Cross-provincial electricity allocation and regional energy development: Evidence from China's ultra-high voltage grid expansion - Bao-Jun Tang; Pei-Yun Xu; Ru Li; Chong-Zhou Wang (Utilities Policy, 2026)

PbrFEN-1 positively regulates pear pollen tube growth and is involved in the self-incompatibility response - Zhi-Heng Sui; Yi-Peng Ye; Ju-Yang Yao; Ya-Ru Wang; Ying Xu; Ce-Xian Cui; Shao-Ling Zhang; Chao Gu (Plant Reproduction, 2026)

A novel inversion method for assessing pipe corrosion condition based on upstream-downstream water quality variation in drinking water distribution systems - Yun-Qiao Zeng; Tian-Yang Zhang; Zhen-Ning Luo; Ling Hu; Bing Geng; Renjie Pan; Zhu Peng; Dai-Xu Zhang; Yi-Ru Chen; Huan He; Mohamed Gamal El-Din; Bin Xu (Water Research, 2026)

Phylogenomics of Tanypodinae (Diptera: Chironomidae) redefines relationships in Procladiini and Tanypodini and supports a new tribe - Xiu-Ru Xiao; Yi-Ni Zhang; Hai-Feng Xu; Zhi-Chao Zhang; Yu-Yi Jiang; Yan-Xin Chen; Chen-Hong Li; Bing-Jiao Sun; Fabio Laurindo da Silva; Xiao-Long Lin (Molecular Phylogenetics and Evolution, 2026)

Characterization of hygroscopicity-based mixing state at four sites in China - Jingye Ren; Fang Zhang; Lu Chen; Jieyao Liu; Wei Xu; Honghao Xu; Zhe Wang; Ru-Jin Huang (Journal of Aerosol Science, 2026)

Combined exposure to wildfire ash and road salts reshapes skin and gut microbiota and reduces fitness in amphibians - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Yue-liang Pan; Wen-jing Dong; Ming-da Xu; Zhi-wen Luo; Li-yong Cui (Environmental Research, 2026)

Polymer-specific oxidative biotransformation of polyethylene and polypropylene microplastics by the stored-grain pest Tribolium castaneum - Sakhawat Shah; Jin-Ru Zhao; Ze-Yu Liu; Yi-Jia Chen; Jie Tang; Karam Khamis Elgizawy; Qiu-Ying Huang; Elvis Genbo Xu; Feng-Lian Yang (Chemical Engineering Journal, 2026)

Apoptotic vesicle-hybridized nanosponges enable dual-phase immunomodulation for targeted periodontitis therapy - Xiao-Ru Xu; Xin-Yan Luo; Lu-Fan Yang; Fei-Ran Wang; Jia-Wei Lu; Bai-Ting Luan; Yuan Yuan; Zi-Qi Zhang; Jin-Yu Liu; Yuan-Yuan Li; Yi-Han Liu; Yu Fu; et al. (Chemical Engineering Journal, 2026)

Metagenomics-guided targeted isolation and mechanistic elucidation of haloalkaliphilic bisphenol A-degrading microorganisms - Sai Yang; Kai-yan Xing; Yue-fei Tao; Jia-yu Wang; Ke-hang Liu; Meng Zhang; Xiang-ru Xu; Lin Zhu; Wei Wei (Bioresource Technology, 2026)

Accumulation, elimination and biotransformation of paralytic shellfish toxins in ark shell Anadara kagoshimensis - Zhuo-Ru Lin; Hui-Xia Geng; Sara A. Cunha; Chang Xu; Ren-Cheng Yu (Marine Pollution Bulletin, 2026)

Carbon dot-based catalytic materials: From photo/electrocatalysis to nanozyme activity - Pei-De Zhu; Chang Liu; Hui Wang; Rong-Yu Yao; Ling-Rui Sun; Xin-Ru Xu; Jing-Wen Jiang; Ying-Sheng Xu; Kun-Peng Lin; Jia-Xing Wu (Journal of Environmental Chemical Engineering, 2026)

From coal gasification slag-derived water glass to monodisperse silica sol: Silicate-species evolution and particle-growth mechanisms - Ru Guo; Jianbo Zhang; Yiyang Li; Hongxiang Xu; Zhengping Zuo; Zhiming Sun; Shaopeng Li; Huiquan Li (Journal of Environmental Chemical Engineering, 2026)

Evolution of lipid profiles, microbiota succession, and potential warmed-over flavor markers in prepared squid (Dosidicus gigas) during extended refrigerated storage: A multi-omics study - Xin Zhang; Rui Tan; Chengxin Lv; Zhiyuan Xiao; Kang Guo; Bin Zhang; Ru Song; Yan Xu; Wei Xia (Food Bioscience, 2026)

Recyclable epoxy vitrimers based on multimechanism-activated transesterification strategies for photothermal conversion and self-healing materials - Huanyu Xu; Liangyi Xing; Ru Wang; Guiyu Chu; Yanmeng Peng; Zhiyue Zhao; Fengjiao Jiang; Shuhua Qi; Hongxia Yan (Chemical Engineering Journal, 2026)

Short-term parental exposure to diazepam disrupts development, behavior, and transcriptional profiles in zebrafish offspring - Qingdong Xu; Yue Xie; Jie Tang; Zhen Su; Kun Chen; Guanghua Mao; Ru-jin Zhao; Yuki Takai; Yohei Shimasaki; Xuchun Qiu (Aquatic Toxicology, 2026)

Intracellular imaging and therapeutic application of liver fibrosis via a microRNA-on self-stacking amplification circuit - Xiao-Meng Sun; Yin-Xiang Chen; Lin-Ru Xu; Rui Bai; Li-Zeng Zhu; Gaoxiang Ma; Lian-Wen Qi; Yu Gu; Qun Liu (Analytica Chimica Acta, 2026)

Chondroitin sulfate: an environmentally friendly immune inducer enhanceing plant resistance to potato virus X and tobacco mosaic virus - Cui-Hong Hao; Wei Xu; Tian-Qi Liang; Yun-Mei Li; Yi-Lin Guan; Ru-Xin Li; Dan-Ya Ju; Chun-E Peng; Li-Zeng Peng; Qing-Bin Wang (Physiological and Molecular Plant Pathology, 2026)

Sublethal cinnamon essential oil induces oxidative stress-driven metabolic reprogramming and attenuates spoilage potential in Psychrobacter faecalis - Yueping Yang; Ru Song; Pengcheng Li; Ye Tao; Xiaoyu Zou; Yan Xu; Rongbian Wei (Food Research International, 2026)

Mechanisms and effects of ozone-pullulanase treatment on multiscale structures and in vitro digestibility of rice starch - Zixuan Liu; Chunfan Guo; Mingyue Chen; Yaping Xu; Jingxuan Ma; Ru Wang; Zhaoxia Wu (Food Chemistry, 2026)

Microbial and environmental determinants of 1-propanol biosynthesis in Jiang-flavor Baijiu fermentation - Wei-Tao Zhai; Han Zhao; Li-Juan Chai; Wei Zhang; Xiao-Juan Zhang; Zhen-Ming Lu; Chuan-Qiang Gao; Guan-Ru Si; Wen-Qing Zhang; Song-Tao Wang; Cai-Hong Shen; Zheng-Hong Xu (Food Microbiology, 2026)

Diniconazole leads to neurotoxicity in zebrafish via triggering TLR4/MyD88-mediated immune-inflammatory responses - Hongying Zhang; Ru Guo; Youjuan Wu; Jiajun Huang; Zijia Yin; Kaiwen Zhao; Xuefeng Liu; Meifeng Li; Zeyin Jiang; Shanghong Wang; Lihua Fan; Chengyu Hu; et al. (Fish & Shellfish Immunology, 2026)

Recovery trajectories of amphibian skin microbiota following ash exposure across translocation and natural recovery scenarios - Qing Tong; Qiu-ru Fan; Hong-xin Jiang; Ming-da Xu; Yue-liang Pan; Li-yong Cui (Environmental Pollution, 2026)

Rational design of covalent-noncovalent coupled interface structures via vacuum-assisted self-assembly/ice-templating dual processes for high thermal conductive composites - Yuqin Liu; Xu Li; Ru Xia; Jiasheng Qian; Bin Wu (Chemical Engineering Journal, 2026)

Shape-memory effect in a flexible hydrogen-bonded organic framework for efficient C2H2/CO2 separation - Chunchen Gao; He Zheng; Wenjie Chen; Yiting Guo; Ru Xu; Ziyi Luo; Qifeng Luo; Xingliang Nie; Xin Lian; Xiongli Liu; Yabing He; Lin Li; et al. (Chemical Engineering Journal, 2026)

A gully catchment-scale model for predicting loess cave density: a case study from the Loess Plateau - Xiaolei Gao; Haopeng Geng; Meiqin Han; Wanying Xu; Ru Liu; Weiming Cheng; Baotian Pan (CATENA, 2026)

Galectin-3 in systemic lupus erythematosus: a meta-analysis - Yang Wu; Li-Na Jiang; Jing-Ru Wu; Yi-Ran Lu; Ting-ting Lu; Ji-Min Zhu; Jing Li; Shanshan Xu; Bai-Kun Li; Cheng-Gui Miao; Yan-Mei Mao (Immunologic Research, 2026)

TRITON: Robust distributed multi-AUV cooperative bearing-only tracking under false alarms and communication uncertainty - Shaoxiong Qiu; Hongli Xu; Jingyu Ru; Wenrui Zhang (Ocean Engineering, 2026)

Phytohormonal orchestration of plant phosphate starvation responses - Kai-Kai Lu; Ru-Feng Song; Yu-Pu Fan; Ling-Yu Xu; Bo-Hao Chen; Shu-Xian Li; Meng-Tian Sun; Guo-Mao Liu; Xiao-Li Huang; Lin Li; Xin-Ru Guo; Feng Ren; et al. (Journal of Plant Physiology, 2026)

Divergent responses of soil respiration to reduced rainfall amount and frequency, and to nitrogen fertilization in a typical steppe - Lan Du; Yan Shen; Jiatao Zhang; Yonghong Luo; Jinbao Zhang; Ru Tian; Zhuwen Xu (Journal of Environmental Management, 2026)

Changes in source-specific health risks of PM2.5-bound trace elements after the residential “coal-to-gas” conversion measure in urban Beijing - Wei Yuan; Ru-Jin Huang; Jing Duan; Jie Guo; Wenjuan Cao; Ting Wang; Jingye Ren; Yanan Zhan; Wei Xu (Journal of Environmental Sciences, 2026)

Two stages of Sn enrichment in granitic magmatism: insights from Sn isotopes of cogenetic minerals - Jia-Xin She; Weiqiang Li; Ru-Cheng Wang; Lei Xie; Chen Liu; Zhihao Xu; Shichao An; Cheng Xu (Geochimica et Cosmochimica Acta, 2026)

Rubidium isotopes reveal no sub-arc melting of altered oceanic crusts in a cold subduction zone - Zi-Qiang Zhong; Ding-Sheng Jiang; Saskia Erdmann; Yi-Xiang Chen; Xia Hu; Zheng Xu; Wei Zhang; Jia-Ru Sheng; Wang-Ye Li; Fang Huang (Geochimica et Cosmochimica Acta, 2026)

A novel sterilization mechanism of cold plasma coupled with low-dose ZnO nanoparticles for food Decontamination: Synergistic reactive species generation and zinc ion release - Hang-Bo Xu; Meng-Ru Du; Zhen Jiao; Pan-Feng Guan; Ruo-Nan Ma (Food Microbiology, 2026)

Achieving ultrahigh water evaporation using g-C3N4/MoS2/chitosan hydrogel@nickel foam evaporator with low enthalpy and optimized scallion-like structure - Zeen Xu; Xingyue Lei; Ru Jiang; Leihao Zhou; Shentao Jiang; Xianqiang Xiong; Qi Wang; Jianbing Li; Huayue Zhu (Chemical Engineering Journal, 2026)

From Lab to Farm: A Low‐Cost Naked‐Eye On‐Site Detecting Platform for Cynoglossus semilaevis Parvovirus Based on Magnetic Beads Adsorption and LAMP ‐ HNB - Shu‐Xia Xue; Si‐Yu Yang; Meng‐Han Xu; Xin‐Rui Liu; Ye‐Xuan Liu; Zi‐Tong Li; Yi‐Xuan Li; Jia‐Ru Hu; Li‐Xian Huang; Xin‐Yi Zhang; Chang Lu; Yu‐Ru Liu; et al. (Journal of Fish Diseases, 2026)
Cynoglossus semilaevis parvovirus (CsPV) is an important pathogen that poses a serious threat to the aquaculture industry. In the absence of vaccines and effective therapeutic drugs, early and sensitive detection of the pathogen is the key measure to prevent and control the outbreaks and epidemics of viral diseases. Currently, the existing detection methods for CsPV are expensive and rely on specialized operations, limiting the application of on‐site detection. There is an urgent need for a low‐cost, user‐friendly detecting platform to prevent fish viral diseases. In this study, we confirmed skin mucus as a target tissue for non‐lethal sampling, established a simple proteinase K digestion, 2% CTAB lysis and silica‐hydroxylated magnetic beads adsorption method for extracting viral genomic DNA from skin mucus and developed a visual one‐pot loop‐mediated isothermal amplification (LAMP) detection method with a sensitivity of 4.69 × 10 1 copies/μL. Validation of the detection platform using clinical samples showed 97% sensitivity and 100% specificity. The cost of reagents for per sample was reduced from 16.6 CNY to 6.2 CNY. The low‐cost naked‐eye on‐site detection platform provides technical support for resource‐limited aquaculture farms to prevent and control emerging viral diseases in Chinese tongue sole.

Unraveling antibiotic fate in a highly urbanized estuary: Spatiotemporal patterns, multi-media partitioning, and contaminant prioritization - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Xiao-Ping Huang (Marine Pollution Bulletin, 2026)

Enhanced photocatalytic fuel cell performance via C/WO3/ZnFe2O4 ternary photoanode for simultaneous wastewater degradation and energy harvesting - Yi Xiao; Ru Zhang; Qi Feng; Hailong Gao; Jiawei Ma; Ting Wu; Yongkui Huang; Longjun Xu; Chenglun Liu (Journal of Environmental Management, 2026)

Ozone-mediated microbial succession and kinetic for refrigerated grass carp (Ctenopharyngodon idella) fillets - Cheng Guo; Guodong Xu; Shanbai Xiong; Tao Yin; Ru Liu; Juan You (International Journal of Food Microbiology, 2026)

Water use complementarity in old-growth mixed forests versus competition in younger successional mixed forests - Ru Huang; Wolfgang Jens-Henrik Meier; Achim Bräuning; Peili Fu; Zexin Fan; Sugam Aryal; Mohsen Arsalani; Haifeng Zhu; Chenxi Xu; Eryuan Liang; Shalik Ram Sigdel; Jussi Grießinger (Agricultural and Forest Meteorology, 2026)

Structural Prior-Guided Adaptive Wavelet Denoising for Single-Channel Dolphin Whistles - Ru Wu; Xiang Zhou; Wen Chen; Peibin Zhu; Xiaomei Xu (Journal of Marine Science and Engineering, 2026)
The continuous, narrowband time-frequency structure of dolphin whistles is an important information carrier for target detection, behavioral analysis, and ecological monitoring in passive acoustic monitoring. However, ocean noise can easily obscure whistle time-frequency contours, blur their boundaries, and cause local discontinuities, thereby reducing the reliability of subsequent acoustic analysis. Existing denoising methods based on transform-domain thresholding and spectral-domain statistical modeling can attenuate background interference to some extent. However, without explicit structural constraints, these methods still have difficulty achieving a satisfactory balance between noise suppression and preservation of the whistle time–frequency structure. To address this problem, this study proposes a Structural Prior-Guided Adaptive Wavelet Denoising (SPG-AWD) method for single-channel unsupervised scenarios. The proposed method introduces structural priors at two levels: adaptive subband selection and terminal node denoising. At the first level, subband nodes are adaptively split, retained, or suppressed based on stationary wavelet packet recursive decomposition and the distribution of candidate structures. At the second level, a structural mask satisfying local grouped-energy and two-dimensional time–frequency connectivity constraints is extracted, and a continuous whistle-presence probability is obtained through a signed distance transform. This probability is then used to jointly guide local noise power spectral density estimation and protective Wiener gain fusion. Simulation results show that, under real recorded background noise and ship noise conditions, SPG-AWD achieves favorable overall denoising performance when the input SNR is higher than −16 dB, while maintaining a more stable balance between target region energy preservation and non-target region noise suppression. Experiments on real recordings further demonstrate that the proposed method can effectively suppress in-band noise components within the whistle-bearing frequency range, better preserve continuous main frequency contours, and improve the overall perceptibility of whistle contours, confirming its applicability to single-channel dolphin whistle denoising in complex underwater noise environments.

Chrs-Net: A Dual-Stream YOLO Network for Underwater RGB–Sonar Object Detection - Chuheng Zhang; Hongli Xu; Pangyi Xiao; Han Wang; Jingyu Ru; Hongxu Yang (Journal of Marine Science and Engineering, 2026)
Underwater RGB–sonar object detection remains challenging due to severe optical degradation, strong sonar noise, and spatial misalignment between heterogeneous modalities. Existing multimodal detectors usually rely on simple feature aggregation or limited structural coupling, which cannot effectively model global cross-modal dependencies or address modality-specific degradation. To address these challenges, we propose Chrs-Net, a YOLOv12-based dual-stream framework for underwater RGB–sonar object detection. The proposed network integrates three key components: a Transformer-based Cross-Modal Communication Fusion module (C-mcf) for global cross-modal interaction and semantic alignment, a Multi-Layer Feature Enhancement module (MLFE) for degraded optical feature enhancement, and a Pinwheel-Shaped Convolution module (PConv) for sonar-side structural feature extraction. In addition, an RGB–sonar object detection dataset is constructed for experimental evaluation by relabeling part of the RGBS benchmark, combining simulator-collected samples, and introducing style-transfer-based augmentation to improve data diversity. Experiments on the constructed dataset yield 94.91% mAP@0.5 and 61.10% mAP@0.5:0.95 on the RGB branch, and 94.00% and 57.13% on the sonar branch, respectively, with an inference speed of 53.6 FPS. Compared with representative single-modality and multimodal detectors, Chrs-Net consistently yields superior detection accuracy and localization performance. These results demonstrate that the combination of global cross-modal communication and modality-specific enhancement is effective for robust underwater RGB–sonar object detection in complex environments.

A regional classification framework integrating AI and causal inference revealing the drivers of lake eutrophication in China - Yong Xu; Ru-Long Ma; Yu-Xi Feng; Bin Zou; Shen-Xin Li; Wen-Ting Huang; Shang-Chen Zhou; Wen-Qiang Peng (Water Research, 2026)

Three undescribed terpenoids from the aerial parts of Alstonia scholaris - Bing-ru Liu; Chun-xiang Xu; Dan Liu; Yue Feng; Rong-tao Li; Jin-dong Zhong (Phytochemistry Letters, 2026)

Synchronized lignocellulosic pyrolysis for activator-free carbon foams: Role of selective hemicellulose removal - Jia-Cheng Ye; Xiao-Ru Meng; Bo Xia; Ting-Yu Bi; Wei Chen; Lu-jiang Xu; Shuai Gao; Zhen Fang (Journal of Environmental Chemical Engineering, 2026)

Persimmon tannin: a novel green enhancer for dual improvement of texture and digestibility in surimi gels - Jingzhi Yan; Shiren Zhang; Kaile Chen; Yanxu Zhuang; Yiyi Cheng; Yan Xu; Ru Song; Haiyan Gao (Food Chemistry, 2026)

Ratio limitation of burnt-bitter-aroma compounds in strong-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Zheng-Juan Zhu; Jing Luo; Ling Xiang; Yan-Hong Xiang; Song-Tao Wang; Wen-Wen Zhang; Qing-Qing Liu; Ting Huang; Zheng-Hong Xu; Yong-Jun Yuan (Food Chemistry, 2026)

From air to adipose: Investigating PM2.5-bound chlorinated paraffins and overweight/obesity in Chinese children and adolescents - Qi Yang; Hai-Xin Tu; Yu He; Ya-Qin Zhang; Muhammad Amjad; Jing-Fu Lai; Jing-Wen Huang; Yun-Ting Zhang; Wan-Ting He; Li-Xia Liang; Wen-Wen Bao; Yang Zhou; et al. (Environmental Research, 2026)

A novel index for the comprehensive assessment of competitive relationships in maize–weed communities using UAV-based hyperspectral data - Caixia Wang; Longzhe Quan; Fei Wang; Jian Xu; Guoxiang Zhang; Xiaojie Li; Chen Ru; Zhaoxia Lou; Chuan Wang; Zhiming Guo (Computers and Electronics in Agriculture, 2026)

Inhibition effect on swelling and permeability enhancement of potassium benzoate in ion adsorption rare earth ore elution - Ziqi Jin; Yuanlai Xu; Ziqi Wang; Shimin Hu; Junhao Pan; Pei Zhao; Ru'an Chi (Minerals Engineering, 2026)

Systematic metabolic engineering of Corynebacterium glutamicum for enhancing L-isoleucine production - Zhi-Han Gong; Ya-Ru Zhang; Jian-Zhong Xu (Systems Microbiology and Biomanufacturing, 2026)

Calcium chloride inhibits water-soaking disorder of fresh-cut cantaloupe through regulating sugar, organic acid, and anaerobic respiration metabolisms - Wanli You; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2026)

Identification and functional analysis of a double-stranded ribonuclease influencing RNAi efficiency in the striped flea beetle, Phyllotreta striolata - Mengli Chen; Keying Chen; Guoxing Chen; Peitong Chen; Dongping Chen; Jiali Qian; Guonian Zhu; Zhanyi Xu; Ru Yan (Pesticide Biochemistry and Physiology, 2026)

From biomass to supercapacitor electrode materials: bamboo derived carbon decorated with MnO2 used in flexible energy storage device - Pengfei Jia; Binyang Liu; Shenao Li; Yizhan Sun; Shuwen Lv; Ru Liu; Yuandong Xu; Xia Zhang; Wei Kong Pang; Peng Li (Fuel, 2026)

Identification of key factors influencing monthly runoff simulation through the integration of deep learning and physically-based hydrological models - Jiyu Zhang; Yufeng Wang; Liangjie Zhao; Ru Sun; Jiayu Sun; Shufei Wang; Shiqin Xu; Zhe Yang (Environmental Modelling & Software, 2026)

Anodic potential and conductive carrier synergistically drive nitrite-free extracellular electron transfer-dependent anaerobic ammonium oxidation (Anammox) in mixed microbial communities - Yang-Guang Xia; Jun-Hong Zhou; Xiao-Li Yang; Fei-Fan Shi; Ru Fan; Jia-Ying Xu (Bioresource Technology, 2026)

Efficient Biosynthesis of Selenium-Enriched Saccharomyces cerevisiae via Siderophore-Assisted selenite uptake and biotransformation - Wen-tao Du; Ya-ru Wei; Xue Zhao; Qiang-qiang Gou; Omer Hassan Ali; Wen-di Wang; Jia-nan Xu; Zai-ping Feng; Xin-guo Zhang (Bioresource Technology, 2026)

A cyclic nucleotide-gated channel gene HcCNGC11 positively regulates salt stress responses in kenaf (Hibiscus cannabinus L.) - Jiao Yue; Canni Chen; Qiuping Wang; Rehmat Ullah; Yuqi Tan; Xu Wang; Huaming Lu; Dengjie Luo; Ru Li; Tao Chen; Peng Chen (Plant Molecular Biology, 2026)

Triterpenoids from Ganoderma angustisporum and their α -glucosidase inhibitory activities - Fan-Ru Xu; Le Zhou; Yu-Cheng Dai; Hai-Sheng Yuan; Yu-Xi Wang (Natural Product Research, 2026)

The variations of the North African monsoon precipitation over the past 200 years - Sainan Liu; Ru Huang; S.-Y. Simon Wang; Chenxi Xu (Palaeogeography, Palaeoclimatology, Palaeoecology, 2026)

Manganese acts as savior rather than accomplice of antibiotic stress: Dual cycles of ROS scavenging and Mnammox - Dong-Jun Hou; Wei-Lin Guo; Qian-Ru Liu; Hong-Wei Yang; Qiu-You Xu; Yun-Fei He; Nian-Si Fan; Ren-Cun Jin (Journal of Water Process Engineering, 2026)

Humic acid facilitates microbial manganese oxidation-driven arsenic remediation in soil across a wide temperature range - Weiwei Zhai; Wenjin Zhang; Lingfeng Dong; Yulong Ru; Yao Xu; Zhanfei He; Daoyong Zhang; Xiangliang Pan (Journal of Environmental Management, 2026)

Preparation of indicator cards for freshness detection of rice with four different processing degrees during storage based on olfactory visualization technology - Wan-ru Liu; Yang Yang; Yue Xu; Bing Wang; Guang Zhang; Xin-yu Xu; Yuan-yuan Wang; Chun-min Ma; Na Zhang (Food Chemistry, 2026)

Relationship of serum polycyclic aromatic hydrocarbon (PAHs) and lung function in adults: Evidence from a large community-based population in Guangzhou, China - Jing-Lin Zhang; Nuo Chen; Shui-Yue Lu; Michael S. Bloom; Shao Lin; Lu-Yin Wu; Li-Xia Liang; Yun-Ting Zhang; Jing-Wen Huang; Muhammad Amjad; Yong-Xiang Tang; Zhao-Huan Gui; et al. (Environmental Research, 2026)

GaAs/GaN-based self-powered catalytic systems driven by tribovoltaic effect enable efficient degradation of azo dyes - Meng-Nan Liu; Yan-Xin Wu; Yu-Tong Sun; Xu Li; Ru Li; Jun Zhang; Yun-Ze Long (Chemical Engineering Journal, 2026)

Tracking the dynamic changes in vegetation belts in China: spatiotemporal insights into climate and human influences - Yong Xu; Yun-Gui Lu; Qiang-Yu Dai; Wen-Ting Huang; Shang-Chen Zhou; Ru-Long Ma; Wen-Qiang Peng; Yu-Xi Feng (Regional Environmental Change, 2026)

DcCAMTA6-DcCML8 promotes GABA accumulation in fresh-cut carrots via transcriptional activation of polyamine metabolism genes - Jinglin Zhang; Wanli You; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2026)

Lactic acid modulates empty-cup aroma persistence in Baijiu via molecular interaction mechanisms: a case study of strong-aroma and soy-sauce-aroma Baijiu - Qing-Ru Liu; Shun-Hua Zhang; Xiao-Juan Zhang; Zheng-Juan Zhu; Ru-Yi Li; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Guan-Yu Fang; Qing-Qing Liu; Yong-Jun Yuan; et al. (Food Chemistry, 2026)

Promoting charge separation via edge activation strategy in conjugated polymers for efficient photocatalytic reaction - Xu Chi; Qian Chen; Chenglong Ru; Zhiming Pan; Wei Ren; Sibo Wang; Zhi-An Lan (Chemical Engineering Journal, 2026)

Microbial functional shifts drive soil phosphorus transformation under long-term nitrogen and water inputs in a semi-arid grassland - Mohsin Mahmood; Ru Tian; Yan Shen; Jiatao Zhang; Lan Du; Anam Ayyoub; Ansa Rebi; Adnan Mustafa; Haoyue Chen; Yiming Zhao; Wenhuai Li; Le Qi; et al. (CATENA, 2026)

Tree of life and conservation of gymnosperms in China - Chang-Wang Ma; Dan Xie; Hong Du; Kai-Yuan Huang; Yuan-Yuan Feng; Zhou-Rui Wei; Xin-Quan Liu; Cheng-Ru Li; Jing-Jing Sun; Xiao-Xin Wei; Zhi-Heng Wang; Wei-Hua Xu; et al. (Science China Life Sciences, 2026)

Dynamic target tracking and pursuit for single AUV with bearing-only constrained sonar - Shaoxiong Qiu; Hongli Xu; Jingyu Ru; Wenrui Zhang (Ocean Engineering, 2026)

Ecological impacts and sustainable development of offshore wind farm pile foundations in the Bodhi Island area - Xiaochen Cheng; Ting Wang; Zhaoming Gao; Xu Wang; Shuai Liu; Yongchao Hu; Beini Deng; Libin Zhang; Xiaoshang Ru (Marine Environmental Research, 2026)

Reducing the healthcare carbon footprint through fully self-service artificial intelligence-powered screening: A comparative simulation study utilizing data from Shanghai City and Lixin Town, China - Yingyan Ma; Xiyuan Shi; Lina Lu; Yi Xu; Juzhao Zhang; Tao Yu; Yajun Peng; Enren Ke; Senlin Lin; Ru Guo; Haidong Zou (Journal of Cleaner Production, 2026)

A dramatic drop in Nb solubility during fractional crystallization of carbonatites triggers Nb ore formation - Ya-Ting Xu; Ru-Cheng Wang; Xu-Dong Che; Fabrice Gaillard; Marion Louvel; Giada Iacono-Marziano; Johann Tuduri (Geochimica et Cosmochimica Acta, 2026)

Rainfall, seasonal variation, and stream type governing the multi-media fate and ecological risks of tire additives and their transformation products in mega-urban streams - Li-Ni Wei; Nian-Nian Wu; Ru Xu; Yuan Liu; Shan Liu; Hai-Yan Zhang; Zi-Tong Li; Yue-Hong Liu; Xiang-Rong Xu; Jian-Liang Zhao; Guang-Guo Ying (Water Research, 2025)

7,8-Dihydroxyflavone attenuates cisplatin-induced cardiomyocyte apoptosis and mitochondrial dysfunction via the p53/Nrf2 pathway - Zhen Tian; Ting-ting Tan; Yu-wei Hu; Jia-tong Yao; Xiao-ting Kang; Jin-yu Zhou; Dong-xu Jia; Qing-liu Li; Ru-jin Liang; Li-mei Zhao; Hua Zhu; Jing Zhao; et al. (Toxicology and Applied Pharmacology, 2025)

A single Drosophila Dscam1 genomic locus generates a vast repertoire of circRNAs facilitated by RNA pairing - Zedong Li; Bingbing Xu; Zhechao Wang; Wenjie Zhang; Jiayan Fu; Lili Wu; Nengcheng Bao; Jinpeng Xie; Ru Yan; Haiyang Dong; Yongfeng Jin (Insect Biochemistry and Molecular Biology, 2025)

Computational-assisted protein engineering to develop thermostable and highly active catalase for industrial and biocatalytic applications - Shuai Xu; Ya-min Chen; Xiang-yu Meng; Ru Pan; Ao-xuan Yan; Zhi-min Li; Zong-lin Li (Bioresource Technology, 2025)

A new norlignan and other compounds from Artemisia frigida Willd - Xin-Ya Dong; Ru-Ya Li; Hong-Xia Tang; Ya-Jie Li; Jun Chen; Jin-Guo Luo; Na Yu; Xiang-Wei Xu; Xu-Dong Zhou (Biochemical Systematics and Ecology, 2025)

Study on the expansion behavior of Halloysite during in-situ leaching ionic rare earth ore - Ziqi Jin; Qi Hu; Qin He; Yuanlai Xu; Xiangyi Deng; Ru'’an Chi (Applied Clay Science, 2025)

Nitrogen enrichment offsets the stimulation of soil respiration by increased precipitation in temperate grasslands - Ru Tian; Jiatao Zhang; Yan Shen; Lan Du; Jinbao Zhang; Shijia Yang; Zhongxiang Liu; Mengle Wang; Zhuwen Xu (Agricultural and Forest Meteorology, 2025)

CaCl2 alleviates water-soaking disorder by attenuating mitochondrial oxidative damage in fresh-cut cantaloupe - Wanli You; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Chemistry, 2025)

Unraveling the enrichment mechanisms of U, Re, Se and V in the Bayinqinggeli Deposit, Northern Ordos Basin through in situ mineralogical analysis - Xiao-Wen Hu; Ming-Xing Ling; Jian-Bing Xu; Fei Xia; De-Ru Xu; Ya-Lun Li; Xiao-Yong Yang; Chao Lu; Hua-Ming Li; Zhen-Cheng Li; Long-Hui Wang; Feng Zhang; et al. (Journal of Geochemical Exploration, 2025)

Polyphenol-synthesized nanoparticles with ALDH3A1 delivery ability for activating estrogen signaling for diabetic wound healing - Xiaoxuan Ma; Yiqiong Liu; Jingsi Jiang; Yi Ru; Ying Luo; Jiankun Song; Zhan Zhang; Ying Zhang; Dan Yang; Haotian Xu; Haiqing Dong; Yongyong Li; et al. (Chemical Engineering Journal, 2025)

A scientific data-driven review of natural product genipin for disease therapy - Dong Xu; Tao Qiao; Kai Gao; Mei-Na Zhao; Wei Zhang; Xing-Ru Tao; Jing-Wen Wang (Phytochemistry Reviews, 2025)

LsMYB44 and LsWRKY75 regulate phenolic accumulation in fresh-cut stem lettuce treated with γ-aminobutyric acid (GABA) - Xueyin Ru; Jinglin Zhang; Wanli You; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2025)

Genomic analysis of Pseudoalteromonas sp. SD03 reveals its potential in chitin hydrolysis - Yu-Xuan Jiang; Wen-Yue Xu; Hui Liu; Si-Qi Lin; Sha-Sha Liu; Xi-Ying Zhang; Yan-Ru Dang (Marine Genomics, 2025)

Effect of exogenous DNP and ATP on storage quality, endogenous energy status and phenolic biosynthesis of shredded cucumber - Wanli You; Yiting Chen; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Journal of Stored Products Research, 2025)

Corrigendum to “Characterization of γ-CD-MOF-stabilized thymol pickering emulsion films with enhanced preservation properties for Basa (Pangasius) fish” [Food Chemistry 476 (2025) 143273] - Yiyi Cheng; Xiaoguo Ying; Xuemei Cai; Yin Chen; Yan Xu; Ru Song; Haiyan Gao (Food Chemistry, 2025)

A bioluminescent enzyme immunoassay based on nanobody-nanoluciferase fusion protein for the detection of fenpropathrin - Luo-Ji Yang; Lin Luo; Ai-Fen Ou; Hao-Sheng Zheng; Ya-Ru Li; Qileng Aori; Änatoly V. Zherdev; Zhen-Lin Xu (Food Bioscience, 2025)

Multispectral analysis and molecular docking simulation of the inhibition mechanism of dietary anthocyanins on acetylcholinesterase - Nuo Wang; Min Zhao; Yue Li; Hao-Yu Xue; Xu Si; Chi Shu; Ying Zhou; Bao-Ru Yang; Sergey S. Makarov; Anton I. Chudetsky; Liang Wang; Ying He; et al. (Food Bioscience, 2025)

An ultrasound-visualized methionine partitioning nano-modulator for enhanced immunotherapy against anti-PD-1 resistant tumors - Yingying Zhao; Beibei Zhang; Shaobo Duan; Yaqiong Li; Yuzhou Wang; Yongchao Wang; Juan Zhang; Rong Huang; Ru Jiang; Rui Zhang; Qi Zhou; Linlin Zhang; et al. (Chemical Engineering Journal, 2025)

Facile blending modification and high-voltage activation strategy enabled long-cycle performance of single crystalline nickel-rich cathode materials - Honglei Liu; Yong Wu; Deli Li; Chengzhi Hu; Lei Zou; Tao Xu; Qiang Wang; Weijian Tang; Dongxu Liu; Ranlin Dong; Ru Song; Zeheng Yang; et al. (Chemical Engineering Journal, 2025)

Endothelial Cell Integrin α6 Regulates Vascular Remodeling Through the PI3K/Akt-eNOS-VEGFA Axis After Stroke - Bing-Qiao Wang; Yang-Ying Duan; Mao Chen; Yu-Fan Ma; Ru Chen; Cheng Huang; Fei Gao; Rui Xu; Chun-Mei Duan (Neuroscience Bulletin, 2025)

Efficient Microbial Production of Selenium Nanoparticles by Selenium-Tolerant Alcaligenes sp. HZ-9-3-3 - Omer Hassan Ali Hassan; Ya-Ru Wei; Zai-Ping Feng; Jia-Mei Pei; Jia-Nan Xu; Wen-Tao Du; Qiang-qiang Gou; Wen-Di Wang; Xue Zhao; Qin-Cui Shi; Xin-Guo Zhang (Current Microbiology, 2025)

Microbial life-history strategies mediate temperature effects on organic carbon pools in black soils - Lihui Lyu; Chaoqun Wang; Kunkun Fan; Jiasui Li; Teng Yang; Guifeng Gao; Ru Sun; Jiao Wang; Xiyuan Xu; Yuxiao Zhang; Yuying Ma; Jiabao Zhang; et al. (Soil Ecology Letters, 2025)

Collision Avoidance of Multi-UUV Systems Based on Deep Reinforcement Learning in Complex Marine Environments - Fuyu Cao; Hongli Xu; Jingyu Ru; Zhengqi Li; Haopeng Zhang; Hao Liu (Journal of Marine Science and Engineering, 2025)
For multiple unmanned underwater vehicles (UUVs) systems, obstacle avoidance during cooperative operation in complex marine environments remains a challenging issue. Recent studies demonstrate the effectiveness of deep reinforcement learning (DRL) for obstacle avoidance in unknown marine environments. However, existing methods struggle in marine environments with complex non-convex obstacles, especially during multi-UUV cooperative operation, as they typically simplify environmental obstacles to convex shapes with sparse distributions and ignore the dynamic coupling between cooperative operation and collision avoidance. To address these limitations, we propose a centralized training with decentralized execution framework with a novel multi-agent dynamic encoder based on an efficient self-attention mechanism. The framework, to our knowledge, is the first to dynamically process observations from an arbitrary number of neighbors that effectively addresses multi-UUV collision avoidance in marine environments with complex non-convex obstacles while satisfying additional constraints derived from cooperative operation. Experimental results show that the proposed method effectively avoids obstacles and satisfies cooperative constraints in both simulated and real-world scenarios with complex non-convex obstacles. Our method outperforms typical collision avoidance baselines and enables policy transfer from simulation to real-world scenarios without additional training, demonstrating practical application potential.

Subgenual anterior cingulate cortex functional connectivity abnormalities in depression: insights from brain imaging big data and precision-guided personalized intervention via transcranial magnetic stimulation - Xiao Chen; Bin Lu; Yu-Wei Wang; Xue-Ying Li; Zi-Han Wang; Hui-Xian Li; Yi-Fan Liao; Daniel M. Blumberger; Francisco Xavier Castellanos; Eduardo A. Garza-Villarreal; Li-Ping Cao; Guan-Mao Chen; et al. (Science Bulletin, 2025)

Thermophilic degradation of sulfamethazine by Geobacillus sp. S-07: pathway and mechanism - Ting Pan; Yan-Yan Zhou; Xu Huang; Jian-Xin Xu; Xiao-Yu Guo; Jian-Qiang Su; Hu Li; Xiao-Ru Yang (Environmental Research, 2025)

Atmospheric microplastic deposition in Guilin karst wetlands: Sources and agricultural impact - Lishan Zhang; Bihong Xu; Zengxian Wei; Xiaolu Liang; Yan Chen; Xuan Ru; Qian Zhang; Shan Zhong (Atmospheric Pollution Research, 2025)

Transcriptome-Wide Sequencing Identifies Non-Coding RNAs and Their Competing Endogenous RNA Networks During the Stages of pPGCLCs-Induced Differentiation - Zhan-Zhong Qiao; Qiu-Yuan Pang; Chang Xu; Xin-Lei Feng; Ming-Xin Zang; Ping Wang; Ying Zhang; Yong-Chao Liu; Qian-Ru Han; Wei Shen; Wei Ge; Shun-Feng Cheng (Stem Cell Reviews and Reports, 2025)

Numeric Modeling of Sea Surface Wave Using WAVEWATCH-III and SWAN During Tropical Cyclones: An Overview - Ru Yao; Weizeng Shao; Yuyi Hu; Hao Xu; Qingping Zou (Journal of Marine Science and Engineering, 2025)
Extreme surface winds and wave heights of tropical cyclones (TCs)—pose serious threats to coastal community, infrastructure and environments. In recent decades, progress in numerical wave modeling has significantly enhanced the ability to reconstruct and predict wave behavior. This review offers an in-depth overview of TC-related wave modeling utilizing different computational schemes, with a special attention to WAVEWATCH III (WW3) and Simulating Waves Nearshore (SWAN). Due to the complex air–sea interactions during TCs, it is challenging to obtain accurate wind input data and optimize the parameterizations. Substantial spatial and temporal variations in water levels and current patterns occurs when coastal circulation is modulated by varying underwater topography. To explore their influence on waves, this study employs a coupled SWAN and Finite-Volume Community Ocean Model (FVCOM) modeling approach. Additionally, the interplay between wave and sea surface temperature (SST) is investigated by incorporating four key wave-induced forcing through breaking and non-breaking waves, radiation stress, and Stokes drift from WW3 into the Stony Brook Parallel Ocean Model (sbPOM). 20 TC events were analyzed to evaluate the performance of the selected parameterizations of external forcings in WW3 and SWAN. Among different nonlinear wave interaction schemes, Generalized Multiple Discrete Interaction Approximation (GMD) Discrete Interaction Approximation (DIA) and the computationally expensive Wave-Ray Tracing (WRT) A refined drag coefficient (Cd) equation, applied within an upgraded ST6 configuration, reduce significant wave height (SWH) prediction errors and the root mean square error (RMSE) for both SWAN and WW3 wave models. Surface currents and sea level variations notably altered the wave energy and wave height distributions, especially in the area with strong TC-induced oceanic current. Finally, coupling four wave-induced forcings into sbPOM enhanced SST simulation by refining heat flux estimates and promoting vertical mixing. Validation against Argo data showed that the updated sbPOM model achieved an RMSE as low as 1.39 m, with correlation coefficients nearing 0.9881.

A new phenolic compound from Persicaria capitata - Lei He; Fei Zhong; Xing-Jun Chen; Ya-Ru Yang; Xue-Long Yan; Ming-Hui He; Xu Zhang; Mu-Zhen Wang; Yong-Qin Zeng; Qin-Feng Zhu; Zhu Zeng; Bo Tu; et al. (Natural Product Research, 2025)

Spatiotemporal distribution and priority assessment of steroids in the estuarine environment: Implications for environmental risk management - Ru Xu; Nian-Nian Wu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Bing Hong; Shen Yu; Xiang-Rong Xu (Marine Pollution Bulletin, 2025)

The role of quorum sensing effector ComA in regulating biofilm formation and surfactin production in Bacillus subtilis ASAG 010 - Ru Jia; Yu Wang; Huachao Wang; Xiao Ji; Faizan Ahmed Sadiq; Xu Wang; Guohua Zhang (Food Bioscience, 2025)

Cyclic loading behavior of earthquake-resilient disc-spring self-centering beam-column joints: An experimental study - Chao Dou; Yi Ru; Long-he Xu (Engineering Structures, 2025)

Unraveling the crucial role of Al distribution in ordered mesoporous silica for ultra-stable CO2 adsorption - Xu Li; Xiangyu Li; Ru Feng; Miaomiao Tan; Yu Feng; Mengmeng Wu; Weiren Bao; Liping Chang; Jiancheng Wang (Chemical Engineering Journal, 2025)

Experimental evidence for viral impact on microbial community, nitrification, and denitrification in an agriculture soil - Hu Li; Sha Zhao; Meng-Ke Gao; Yanyan Zhou; Bo Xu; Le-Yang Yang; Xiao-Ru Yang; Jian-Qiang Su (Journal of Hazardous Materials, 2025)

How does digital industry agglomeration drive carbon peaking and carbon neutrality in China? The role of digital technology innovation - Ru-Yu Xu; Ke-Liang Wang (Journal of Cleaner Production, 2025)

Efflux pumps of Pseudomonas aeruginosa and their regulatory mechanisms underlying multidrug resistance - Wen-Ru Li; Zhi-Qing Zhang; Kang Liao; Qing-Shan Shi; Xu-Bin Huang; Xiao-Bao Xie (International Biodeterioration & Biodegradation, 2025)

Characterization of γ-CD-MOF-stabilized thymol Pickering emulsion films with enhanced preservation properties for Basa (Pangasius) fish - Yiyi Cheng; Xiaoguo Ying; Xuemei Cai; Yin Chen; Yan Xu; Ru Song; Haiyan Gao (Food Chemistry, 2025)

Recent duplications and rare structural variations revealed by comparative sequence analysis of low molecular weight glutenin subunits (LMW-GS) genes re-identified using LMWgsFinder in 26 genomes of the grass family - Shengli Zhang; Xiaojing Shan; Yun Wang; Tairui Lu; Daxing Xu; Han Gong; Yuchao Fan; Yuanyuan Guan; Junjie Zhao; Haili Sun; Dongfang Li; Haiyan Hu; et al. (Theoretical and Applied Genetics, 2025)

Daily Evolution of Three-Dimensional Structure of a Subsurface Anticyclonic Eddy and Eddy-Induced Swirl Transport in the Canada Basin - Fan Xu; Haiyan Li; Ru Wang; Zhiqiang Wen; Kun Yang; Menghao Zhang (Journal of Ocean University of China, 2025)

Flotation separation of parisite from calcium-bearing gangue minerals using polyaspartic acid as a depressant - Jingyang Shi; Jing Lv; Jieliang Wang; Zhao Cao; Wenda Lu; Yongdan Cao; Xu Wu; Xiaoping Wang; Jiayan Tang; Zhenyue Zhang; Ru-an Chi (Minerals Engineering, 2025)

Collagenases from hepatopancreas and muscle of Litopenaeus vannamei: Purification, characterization and comparison of their behaviors in collagen degradation - Xu-Chen Xiao; Jia-Yin Huang; Yu-Lei Chen; Kai-Yuan Cao; Ru-Qing Yang; Duan-Quan Lin; Shu-Jun Hong; Yu-Ting Yang; Min-Jie Cao (Food Chemistry, 2025)

Targeted restoration of endothelial hypoxic response prevents angiogenic bone loss against liver fibrosis - Nan Zhang; Sheng-Feng Bai; Jia-Ning Liu; Xin Huang; Lu Liu; Yu-Ru Gao; Si-Qi Ying; Chen-Xi Zheng; Hao-Kun Xu; Ji Chen; Xiao Lei; Yu-Bo-Han Zhang; et al. (Chemical Engineering Journal, 2025)

Synthesis of hollow HC-Ni0.96S@MXene/C nanobox as advanced anode for lithium-ion and sodium-ion battery - Song-Yi Liao; Jing Chen; Dao-Ren Deng; Cai-Yun Wu; Selina X. Yao; Yi Wang; Yu-Ming Ru; Xiao-Yan Li; Xu-Gang Shu; Yong-Gang Min (Chemical Engineering Journal, 2025)

Ribosomal protein S3A (RPS3A), as a transcription regulator of colony-stimulating factor 1 (CSF1), promotes glioma progression through regulating the recruitment and autophagy-mediated M2 polarization of tumor-associated macrophages - Liang Zhang; Kun Wang; Fei Li; Lingxue Zhang; Lin Wu; Ru Tie; Kamulan Litifu; Yujie Fu; Simeng Liu; Jiaxin Ni; Pan Chang; Jun Xu; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2025)

Unmet needs of patients with intravascular large B-cell lymphoma: three case reports and a literature review - Xian Li; Ru Luo; Jiaming Xu; Xueli Jin; Weiqin Wang; Xibin Xiao; Wenbin Qian (Journal of Zhejiang University-SCIENCE B, 2025)

Electrochemically enhanced micro-electrolytic ceramic substrate infiltration system as an efficient approach for treatment of imidacloprid wastewater - Ru Zhang; Weiwei Zhang; Chengcheng Bu; Guangyao Chen; Shuyun Li; Yuchen Han; Haibin Ma; Anyong Xu; Desheng Wang; Limin Ma (Environmental Monitoring and Assessment, 2025)

Erratum to: CXCL16 promotes proliferation of head and neck squamous cell carcinoma by regulating GPX1-mediated antioxidant levels - Ru He; Hongyi Jiang; Chengchi Zhang; Yuan Chen; Wenshun Liu; Xinyue Deng; Xiaozheng Zhu; Yunye Liu; Chuanming Zheng; Yining Zhang; Chengying Shao; Yanting Duan; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Structural and electronic regulation of transition metal borides: from controllable synthesis to industrial alkaline water splitting - Na Xu; Xin-Ru Li; Denghao Ouyang; Guodong Li; Shijian Cheng; Zhongmin Tang; Yong-Ming Chai; Bin Dong (Fuel, 2025)

Designing multilayer interlocked architectures with vertical LDH nanosheets in ZIF-67 composite membranes for upgrading CO2 separation - Yan-Mei Zhang; Li-Hao Xu; Xiao-Xue Hu; Bing-Hong Chen; Xin-Ru Chen; Qian-Qian Li; Heng Mao; Zhi-Ping Zhao (Chemical Engineering Journal, 2025)

Leveraging Deep Learning to Extract Raindrop Size Gamma Distribution Parameters from Wind Profile Radar Data - Yu Huang; Zhiqun Hu; Lin Li; Ru Zhou; Xu Lu; Mengyu Huang (Journal of Meteorological Research, 2025)

Sediment Provenance and Facies Analysis of the Huagang Formation in the Y-Area of the Central Anticlinal Zone, Xihu Sag, East China Sea - Xiao Ma; Wei Yan; Yi Yang; Ru Sun; Yue Chao; Guoqing Zhang; Chao Yang; Shudi Zhang; Dapeng Su; Guangxue Zhang; Hong Xu (Journal of Marine Science and Engineering, 2025)
Recent breakthrough exploration wells in the Huagang Formation in the Y-area of the central anticlinal zone of the Xihu Sag have confirmed the significant exploration potential of structure–lithology complex hydrocarbon reservoirs. However, limited understanding of the provenance system, sedimentary facies, and microfacies has hindered further progress in complex hydrocarbon exploration. Analysis of high-precision stratigraphic sequences and seismic facies data, mudstone core color, grain-size probability cumulative curves, core facies, well logging facies, lithic type, the heavy-mineral ZTR index, and conglomerate combinations in drilling sands reveals characteristics of the source sink system and provenance direction. The Huagang Formation in the Y-area represents an overall continental fluvial delta sedimentary system that evolved from a braided river delta front deposit into a meandering river channel large-scale river deposit. The results indicate that the primary provenance of the Huagang Formation in the Y-area of the Xihu Sag is the long-axis provenance of the Hupi Reef bulge in the northeast, with supplementary input from the short-axis provenance of the western reef bulge. Geochemical analysis of wells F1, F3, and G in the study area suggests that the prevailing sedimentary environment during the period under investigation was characterized by anoxic conditions in nearshore shallow waters. This confirms previous research indicating strong tectonic reversal in the northeast and a small thickness of the central sand body unrelated to the flank slope provenance system. The aforementioned findings deviate from conventional understanding and will serve as a valuable point of reference for future breakthroughs in exploration.

The association between anthropogenic heat and parent-report symptoms of childhood attention deficit hyperactivity disorder in China: A novel perspective reflecting climate change - Tao Yu; Yue Wen; Pei-Pei Dong; Ming-Kun Sun; Samantha E. Qian; Mario Schootman; Michael G. Vaughn; Shu-Li Xu; He-Hai Huang; Feng-Wen Shan; Shi-Fu Zhu; Jing-Yao Wang; et al. (International Journal of Hygiene and Environmental Health, 2025)

Mechanism of enhanced quality of Acetes chinensis powder-Alaska Pollock surimi: Gel properties, rheological properties, micro-structure - Qianqian Li; Jiehui Feng; Ru Jia; Huamao Wei; Tao Huang; Jinjie Zhang; Dalun Xu; Wenge Yang; Gaoshang Li (Food Research International, 2025)

Is there an association between eye-level greenness and childhood hypertension using street view? Findings from the Seven Northeastern Cities study in China - Huang-Min Yang; Jing-Yao Wang; Cheng Li; Ya-Qin Zhang; Ruoyu Wang; Qi Yang; Yao Yao; Zilong Wang; Shu-Li Xu; He-Hai Huang; Qian-Sheng Hu; Ru-Qing Liu; et al. (Environmental Research, 2025)

Synergistic toxicity of cadmium and triadimefon on the microbiota and health of Rana dybowskii tadpoles - Xiao-yun Han; Peng Guo; Qiu-ru Fan; Qing-bo Zhou; Ming-da Xu; Xin-zhou Long; Li-yong Cui; Qing Tong (Comparative Biochemistry and Physiology Part C: Toxicology & Pharmacology, 2025)

Thresholding Dolphin Whistles Based on Signal Correlation and Impulsive Noise Features Under Stationary Wavelet Transform - Xiang Zhou; Ru Wu; Wen Chen; Meiling Dai; Peibin Zhu; Xiaomei Xu (Journal of Marine Science and Engineering, 2025)
The time–frequency characteristics of dolphin whistle signals under diverse ecological conditions and during environmental changes are key research topics that focus on the adaptive and response mechanisms of dolphins to the marine environment. To enhance the quality and utilization of passive acoustic monitoring (PAM) recorded dolphin whistles, the challenges faced by current wavelet thresholding methods in achieving precise threshold denoising under low signal-to-noise ratio (SNR) are confronted. This paper presents a thresholding denoising method based on stationary wavelet transform (SWT), utilizing suppression impulsive and autocorrelation function (SI-ACF) to select precise thresholds. This method introduces a denoising metric ρ, based on the correlation of whistle signals, which facilitates precise threshold estimation under low SNR without requiring prior information. Additionally, it exploits the high amplitude and broadband characteristics of impulsive noise, and utilizes the multi-resolution information of the wavelet domain to remove impulsive noise through a multi-level sliding window approach. The SI-ACF method was validated using both simulated and real whistle datasets. Simulated signals were employed to evaluate the method’s denoising performance under three types of typical underwater noise. Real whistles were used to confirm its applicability in real scenarios. The test results show the SI-ACF method effectively eliminates noise, improves whistle signal spectrogram visualization, and enhances the accuracy of automated whistle detection, highlighting its potential for whistle signal preprocessing under low SNR.

Knockdown and insecticidal activities of pyrethrum, dimefluthrin and meperfluthrin against Aedes aegypti and Aedes albopictus - Mengli Chen; Ru Yan; Zhanyi Xu; Qiaoling Zhou; Yuyan Wu (International Journal of Tropical Insect Science, 2025)

Insight into the mechanism of setting temperature and time on gel properties of Solenocera crassicornis surimi - Jiafang Lu; Jingjing Tong; Dalun Xu; Huamao Wei; Tao Huang; Wenge Yang; Ru Jia (Food Research International, 2025)

Effect of vacuum frying on the structure and bioactivity of proanthocyanidins in Chinese quince (Chaenomeles sinensis Koehne) fruit - Yu Lou; Xu Fang; Zi-Cheng Yang; Jia-Lin Fei; Yu-Ru Feng; Zhao Qin; Hua-Min Liu; Yu-Xiang Ma; Xue-De Wang (Food Chemistry, 2025)

Exploration of the impact of different drying methods on the quality of Gastrodia elata: A study based on drying kinetics and multidimensional quality evaluation - Ming-xuan Li; Bin Wang; Yu Li; Xin-ru Nie; Jing Mao; Qiang Guo; Nuo Xu; Rao Fu; Zhi-jun Guo; Xiao-li Zhao; Zhen-hua Bian; Tu-lin Lu; et al. (Food Chemistry, 2025)

Advanced fabrication of three-dimensional bicontinuous MXene/agarose composite monoliths for high-selective rapid separation of antibodies - Xiang-Dong Xu; Jing Li; Jun-Qi Zhang; Yuan Peng; Chen-Mei Sun; Ru-Qi Liang; Jian-Bo Qu (Chemical Engineering Journal, 2025)

Ultra-low energy wastewater remediation: Excellent properties of smart adsorption membranes - Yun-Hao Xia; Ying-Ying Gui; Jia-Hua Zhou; Gui-E Chen; Zhe-Ru Shi; Zhen-Liang Xu (Chemical Engineering Journal, 2025)

Data imbalance causes underestimation of high ozone pollution in machine learning models: A weighted support vector regression solution - Ling Zhen; Baihua Chen; Lin Wang; Lin Yang; Wei Xu; Ru-Jin Huang (Atmospheric Environment, 2025)

Tetrachlorantraniliprole induces neurodevelopmental toxicity through oxidative stress-mediated apoptosis and dysregulation of Wnt signaling pathway - Ru Guo; Youjuan Wu; Tingting Yu; Chen Guo; Zijia Yin; Guannan Zhao; Meifeng Li; Huiling Mao; Chengyu Hu; Xiaowen Xu (Aquatic Toxicology, 2025)

Prediction of the potential dispersal corridors for Gaoligong hoolock gibbon in northern Yingjiang, Yunnan, China - Yong-liang Zhu; Meng-ling Xu; Li-xiang Zhang; Peng Li; Bao Jin; An-ru Zuo; Xue-long Jiang; Zhen-hua Guan (Journal for Nature Conservation, 2025)

Enhancing capacitive desalination efficiency via atomically dispersed Fe in N/P doped carbon material - Zhirou Wang; Xinhua Huang; Yuzudi Tong; Tong Wang; Mai Xu; Ru Li; Guangzhi Hu (Chemical Engineering Journal, 2025)

Customized low heat resistance interfacial structure endowing multifunctional composite with excellent thermal conductivity - Xu Li; Bin Wu; Ying Lv; Ru Xia; Jiasheng Qian (Chemical Engineering Journal, 2025)

CXCL16 promotes proliferation of head and neck squamous cell carcinoma by regulating GPX1-mediated antioxidant levels - Ru He; Hongyi Jiang; Chengchi Zhang; Yuan Chen; Wenshun Liu; Xinyue Deng; Xiaozheng Zhu; Yunye Liu; Chuanming Zheng; Yining Zhang; Chengying Shao; Yanting Duan; et al. (Journal of Zhejiang University-SCIENCE B, 2025)

Isoalcanivorax beigongshangi sp. nov., isolated from the fermented grains of Chinese baijiu - Tong-Xi Zhang; Yi-Ming Li; Hao-Yue Gu; Ru Zhang; Zhan-Bin Sun; Han-Xu Pan; Qing Ren (Antonie van Leeuwenhoek, 2025)

Association of anthropogenic heat with asthma and related symptoms among children in China: A novel index reflecting climate change - Feng-Wen Shan; Xuan Liu; Ming-Kun Sun; Zhengmin Qian; Michael G. Vaughn; Niraj R. Chavan; Shu-Li Xu; He-Hai Huang; Zhao-Huan Gui; Ru-Qing Liu; Li-Wen Hu; Li-Zi Lin; et al. (Sustainable Cities and Society, 2024)

Zebrafish FKBP5 facilitates apoptosis and SVCV propagation by suppressing NF-κB signaling pathway - Zijia Yin; Hongying Zhang; Kaiwen Zhao; Yulong Liu; Ru Guo; Pengxia Xu; Guannan Zhao; Menglei Hu; Chengyu Hu; Xiaowen Xu (Fish & Shellfish Immunology, 2024)

PRDX1 Interfering Peptide Disrupts Amino Acids 70–90 of PRDX1 to Inhibit the TLR4/NF-κB Signaling Pathway and Attenuate Neuroinflammation and Ischemic Brain Injury - Xiang-Yu Ma; Cheng-yu Qi; Xing-yi Xu; Hui Li; Chang-Dong Liu; Xiang-Ru Wen; Yan-Yan Fu; Yan Liu; Jia Liang; Cheng-Yu Huang; Dan-Dan Li; Yan Li; et al. (Molecular Neurobiology, 2024)

Hydrogel encapsulating gold nanoparticles for targeted delivery of nitroglycerin to reduce post-cardiac dysfunction inflammation by inhibiting the Wnt/β-catenin signaling pathway - Ruixuan Li; Aixia Xu; Ye Chen; Yihui Li; Ru Fu; Weihong Jiang; Xiaogang Li (Inflammopharmacology, 2024)

Nitrogen addition alleviates the negative effects of reduction in precipitation on soil multifunctionality in a typical steppe - Yan Shen; Yonghong Luo; Lan Du; Ru Tian; Wenqian Shao; Jiatao Zhang; Na Li; Jinbao Zhang; Shan Wang; Mohsin Mahmood; Zhuwen Xu (Applied Soil Ecology, 2024)

KLK7, KLK10, and KLK11 in Papillary Thyroid Cancer: Bioinformatic Analysis and Experimental Validation - Tao Ni; Ru-hua Zhao; Jing-fang Wu; Chao-you Li; Gang Xue; Xu Lin (Biochemical Genetics, 2024)

The different impacts of functional network centrality and connectivity on the complexity of brain signals in healthy control and first-episode drug-naïve patients with major depressive disorder - Shanling Ji; Wei An; Jing Zhang; Cong Zhou; Chao-Gan Yan; Xiao Chen; Li-Ping Cao; Wei Chen; Yu-Qi Cheng; Yi-Ru Fang; Qi-Yong Gong; Wen-Bin Guo; et al. (Brain Imaging and Behavior, 2024)

Revisiting the impact of temperature on ground-level ozone: A causal inference approach - Baihua Chen; Ling Zhen; Lin Wang; Haobin Zhong; Chunshui Lin; Lin Yang; Wei Xu; Ru-Jin Huang (Science of The Total Environment, 2024)

Proteomic analysis revealed the deterioration of surimi gelling capability to fish stress during transportation - Zhiying Xiang; Tao Yin; Zenan Huang; Ziaur Rahman; Yongsawatdigul Jirawat; Tanye Xu; Qilin Huang; Juan You; Ru Liu; Hong Yang (Food Research International, 2024)

Impacts of food additives on gut microbiota and host health - Ping Li; Ru Qu; Ming Li; Ping Sheng; Liang Jin; Xiaochang Huang; Zhenjiang Zech Xu (Food Research International, 2024)

γ-aminobutyric acid treatment inhibits browning and promotes storage quality by regulating reactive oxygen species and membrane lipid metabolism in fresh-cut stem lettuce - Xueyin Ru; Wanli You; Jinglin Zhang; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Chemistry, 2024)

Effects of dielectric barrier discharge cold plasma treatment on quality maintenance, energy and γ-aminobutyric acid accumulation of fresh-cut carrots - Wanli You; Xianwei Meng; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Control, 2024)

Cadmium causes cerebral mitochondrial dysfunction through regulating mitochondrial HSF1 - Chen-Xi Li; Milton Talukder; Ya-Ru Xu; Shi-Yong Zhu; Yu-Xiang Wang; Jin-Long Li (Environmental Pollution, 2024)

The impact of digital technology innovation on green total-factor energy efficiency in China: Does economic development matter? - Ru-Yu Xu; Ke-Liang Wang; Zhuang Miao (Energy Policy, 2024)

Lead carbanion anchoring for surface passivation to boost efficiency of inverted perovskite solar cells to over 25% - Jinlong Hu; Xu Jiang; Donghui Lan; Dongmei Xie; Weiyan Wang; Ru Zhang; Huahang Lai; Siow Hwa Teo; Zhenhua Xu; Hai-Qiao Wang (Chemical Engineering Journal, 2024)

Role of Nitrogen-doping in porous carbon for enlarging working voltage window of aqueous supercapacitors in neutral electrolyte - Shao-Wen Xu; Jing-Xuan Dai; Meng-Die Wang; Ru-Yue Zhu; Yong-Qing Zhao (Chemical Engineering Journal, 2024)

Ubiquity and ecological risks of conjugated steroids cannot be overlooked: First evidence from estuarine sediments - Fei Tian; Shan Liu; Ru Xu; Nian-Nian Wu; Shuang-Shuang Liu; Yuan-Yue Cheng; Qian Xiong; Zhen-Zhao Tang; Lin-Bao Zhang; Zhe Zhang; Hai-Gang Chen (Marine Pollution Bulletin, 2024)

Corrigendum to “CLAUDIN7 modulates trophectoderm barrier function to maintain blastocyst development in pigs” [Theriogenology 158 (2020) 346–357 10.1016/j.theriogenology.2020.09.038] - Di Gao; Tengteng Xu; Xin Qi; Wei Ning; Shang Ren; Zhenyuan Ru; Kaiyuan Ji; Yangyang Ma; Tong Yu; Yunsheng Li; Zubing Cao; Yunhai Zhang (Theriogenology, 2024)

Bond performance and constitutive model of steel bar in G-UHPC under cyclic loading - Ting Yang; Shenchun Xu; Pengcheng Yuan; Dayang Wang; Ru Liao; Yekai Yang; Ruizhe Shao; Chengqing Wu (Engineering Structures, 2024)

Understanding the evolution of molybdenum-nitrogen doped carbon with long-term durability for efficient oxygen reduction reaction - Xingyu Luo; Bingbao Mei; Ru Feng; Xiaofeng Xu; Zhongyan Zhang; Mingyu Ou; Fanfei Sun; Huajun Zheng; Meiqin Shi (Chemical Engineering Journal, 2024)

Enhancing osseointegration and angiogenesis of Titanium implants through KMnO4-Modified Montmorillonite nano-clay coating - Lifeng Xiong; Binwei Dai; Baodi Yin; Kendrick Hii Ru Yie; Haobo Sun; Yang Liu; Zheyuan Liu; Ahmed S. Mahany; Huan Cheng; Lihua Xu; Peng Gao; Lei Lu; et al. (Chemical Engineering Journal, 2024)

Seed priming using different agents can alleviate salt stress in kenaf (Hibiscus cannabinus L.) by activating antioxidant system and related genes expression - Renxue Li; Dengjie Luo; Muzammal Rehman; Xin Li; Caijin Wang; Shan Cao; Guofeng Xu; Meng Wang; Canni Chen; Jingzhi Nie; Ru Li; Tao Chen; et al. (Physiology and Molecular Biology of Plants, 2024)

Improved prediction of swimming talent through random forest analysis of anthropometric and physiological phenotypes - Cheng Liu; Bingxiang Xu; Kang Wan; Qin Sun; Ruwen Wang; Yue Feng; Hui Shao; Tiemin Liu; Ru Wang (Phenomics, 2024)

Drought and nitrogen deposition regulate plant nutrient resorption in a typical steppe - Yonghong Luo; Yan Shen; Ahmed Salah Elrys; Lan Du; Mohsin Mahmood; Jiatao Zhang; Haiyan Ren; Jinbao Zhang; Na Li; Ru Tian; Wenqian Shao; Ahmed S.M. Elnahal; et al. (Agriculture, Ecosystems & Environment, 2024)

Applications in Pickering emulsions of enhancing preservation properties: Current trends and future prospects in active food packaging coatings and films - Yiyi Cheng; Xuemei Cai; Xin Zhang; Yadong Zhao; Ru Song; Yan Xu; Haiyan Gao (Trends in Food Science & Technology, 2024)

The irregular developmental duration mainly caused by the broad-complex in Chilo suppressalis - Zhi-Ling Zhang; Qing-Yu Xu; Ru Zhang; Chen Shen; Hai-Bo Bao; Guang-Hua Luo; Ji-Chao Fang (Pesticide Biochemistry and Physiology, 2024)

Water–Rock reactions in the acid leaching of Uranium: Hydrochemical characteristics and reaction mechanisms - Bing Wang; Yue Luo; Xun Li; Ya–zhou Liu; Chang–rui Xu; Yu–xiu Zheng; Yan–hong Zhang; Yi–ru Zhou (Journal of Hydrology, 2024)

Land surface response to groundwater drawdown and recovery in Taiyuan city, Northern China, analyzed with a long-term elevation change measurements from leveling and multi-sensor InSAR - Wei Tang; Xiangjun Zhao; Jinyang Wang; Mahdi Motagh; Huipeng Xu; Zhemin Ru; Yiming Wang (Journal of Hydrology, 2024)

Supramolecular assembly of dual crosslinked nanocomposite polysaccharides hydrogel: Integration of injectable, self-healing, and pH-responsive platform for sustained delivery of polyphenols - Fatima-ezzahra Ettoumi; Hao Huang; Yanqun Xu; Lei Wang; Qiaomei Ru; Yichen Hu; Liang Zou; Zisheng Luo (Food Hydrocolloids, 2024)

High yield, good eating quality, and high N use efficiency for medium hybrid indica rice: From the perspective of balanced source-sink relationships at heading - Haibing He; Chao Hu; Haochong Xu; Ru Yang; Cuicui You; Jian Ke; Qiangqiang Zhang; Liquan Wu (European Journal of Agronomy, 2024)

Three new lanostane triterpenoids and two new amides from Alternaria sp. with NLRP3 inflammasome inhibitory activity - De-Wen Bi; Jian- Feng; Wen-Hui Pang; Peng-Yun Yang; Yao-Jun Xu; Muhammad Aurang Zeb; Meng-Ru Wang; Xing-Jie Zhang; Xiao-Li Li; Rui-Han Zhang; Wei-Guang Wang; Wei-Lie Xiao (Natural Product Research, 2024)

A comprehensive review of matcha: production, food application, potential health benefits, and gastrointestinal fate of main phenolics - Jian-Hui Ye; Qi-Ting Fang; Lin Zeng; Ru-Yi Liu; Lu Lu; Jun-Jie Dong; Jun-Feng Yin; Yue-Rong Liang; Yong-Quan Xu; Zhong-Hua Liu (Critical Reviews in Food Science and Nutrition, 2024)

A cyclic nucleotide-gated channel gene HcCNGC21 positively regulates salt and drought stress responses in kenaf (Hibiscus cannabinus L.) - Canni Chen; Qijing Wu; Jiao Yue; Xu Wang; Caijin Wang; Rujian Wei; Ru Li; Gang Jin; Tao Chen; Peng Chen (Plant Science, 2024)

Glucoconjugated monoterpene indole alkaloids with xanthine oxidase inhibitory activity from Ophiorrhiza japonica - Bao-Bao Shi; Fan Xu; Guang-Ru Zhang; Yu He; Qing Liu; Meng-Lin Feng; Zheng-Hui Li; Ji-Kai Liu (Phytochemistry, 2024)

Glycine to valine substitution in the short intracellular linkers of domain II enhances I1011M-mediated sodium channel resistance to Type I pyrethroids, but not Type II pyrethroids - Mengli Chen; Xiangyi Zhou; Guoxing Chen; Zhanyi Xu; Jiali Qian; Guonian Zhu; Ru Yan (Pesticide Biochemistry and Physiology, 2024)

Accurate and precise in situ determination of beryllium contents in beryllium minerals using ablation spot size of 13 μm by LA–ICP–MS - Wen-Kai Jin; Xu-Dong Che; Ru-Cheng Wang; Huan Hu; Can Rao; Wen-Lan Zhang; Xiao-Feng Li (Journal of Geochemical Exploration, 2024)

Ecological restoration largely alleviates livestock grazing pressure in a montane grassland - Xiao-lian Qi; Hao-jie Xu; Ru-yu Teng; Tian Chen; Xu-dong Wang (Journal of Cleaner Production, 2024)

Green tea polyphenols reduced Porphyromonas gingivalis virulence and ameliorated aggravated gut inflammation by improving immunity and gut microbiota dysbiosis - Ming Li; Ru Qu; Ping Li; Xuan Mo; Juan Liu; Zhenjiang Zech Xu (Food Bioscience, 2024)

Bud shapes dictate tiller–rhizome transition in African perennial rice (Oryza longistaminata) - Kai Wang; Yufei Lu; Suwen Jing; Ru Yang; Xianjie Xu; Yourong Fan; Jiangyi Yang (Theoretical and Applied Genetics, 2024)

TNFAIP1 promotes macrophage lipid accumulation and accelerates the development of atherosclerosis through the LEENE/FoxO1/ABCA1 pathway - Can Xu; Jun Meng; Xiao-Hua Yu; Ru-Jing Wang; Mei-Ling Li; Shan-Hui Yin; Gang Wang (Journal of Physiology and Biochemistry, 2024)

Rapid, sensitive, and visual detection of pseudorabies virus with an RPA-CRISPR/EsCas13d-based dual-readout portable platform - Dong You; Tong Xu; Bing-Zhou Huang; Fang Wu; Li-Shuang Deng; Zhe-Yan Liu; Liang-Peng Ge; Zuo-Hua Liu; Jing Sun; Xiu Zeng; Yuan-Cheng Zhou; Si-Yuan Lai; et al. (Analytica Chimica Acta, 2024)

Asperidulins A and B, two new prenylxanthone derivatives from an apple-derived fungus Aspergillus nidulans KIB-HACM-01 - Peng Lai; Li Wang; Chenjie Deng; Yixin Xu; Xiao-Yan Ma; Chun-Ru Cheng; Sheng-Xiong Huang (Natural Product Research, 2024)

Distance-decay equations of antibiotic resistance genes across freshwater reservoirs - Zhao-Feng Guo; Kiranmoy Das; Wiebke J. Boeing; Yao-Yang Xu; Edoardo Borgomeo; Dong Zhang; Si-Cheng Ao; Xiao-Ru Yang (Water Research, 2024)

Nano‑selenium alleviates cadmium-induced blood-brain barrier destruction by restoring the Wnt7A/β-catenin pathway - Chen-Xi Li; Milton Talukder; Zhao-Yi Wang; Shi-Yong Zhu; Ya-Ru Xu; Xue-Nan Li; Jin-Long Li (Science of The Total Environment, 2024)

Exogenous CaCl2 delays flesh softening by inhibiting the degradation of cell wall in fresh-cut cantaloupe - Wanli You; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2024)

Chemical constituents with antioxidant activity from the branches and leaves of Hultholia mimosoides - Ru Feng; Jia-Xin Xu; Xiao-Yi Luan; Xiao-Ning Wang; Tao Shen; Dong-Mei Ren; Xiao-Ling Wang (Phytochemistry, 2024)

Exogenous chlorogenic acid inhibits quality deterioration in fresh-cut potato slices - Wanli You; Chunfei Wang; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Chemistry, 2024)

Identification and functional analyses of CD4-1+ cells in grass carp (Ctenopharyngodon idella) - Xue-Qing Han; Yi-Ru Pan; Ya-Qin Zhong; Tian-Tian Tian; Xun Liu; Xu-Jie Zhang; Yong-An Zhang (Fish & Shellfish Immunology, 2024)

Prenatal exposure to fenvalerate causes depressive-like behavior in adulthood by inhibiting brain-derived 5-HT synthesis - Hui-Min Zhu; Bo Wang; Tao Wang; Jing Shao; Hui-Ru Chen; Chi Zhang; Li-Hua Xu; Jing-Jing Li; Min Wang; De-Xiang Xu; Xiu-Hong Meng (Environmental Pollution, 2024)

Whole exome sequencing analyses reveal novel genes in telomere length and their biomedical implications - Wei-Shi Liu; Bang-Sheng Wu; Liu Yang; Shi-Dong Chen; Ya-Ru Zhang; Yue-Ting Deng; Xin-Rui Wu; Xiao-Yu He; Jing Yang; Jian-Feng Feng; Wei Cheng; Yu-Ming Xu; et al. (GeroScience, 2024)

Cysteine and glycine-rich protein 2 is crucial for maintaining the malignant phenotypes of gliomas through its action on Notch signalling cascade - Lingtong Liu; Fei Li; Lingxue Zhang; Yingying Cheng; Lin Wu; Ru Tie; Xiaobing Jiang; Wenwen Gao; Bochuan Liu; Yao Wei; Pan Chang; Jun Xu; et al. (Toxicology and Applied Pharmacology, 2024)

Reduction in precipitation amount, precipitation events, and nitrogen addition change ecosystem carbon fluxes differently in a semi-arid grassland - Lan Du; Yonghong Luo; Jiatao Zhang; Yan Shen; Jinbao Zhang; Ru Tian; Wenqian Shao; Zhuwen Xu (Science of The Total Environment, 2024)

Neoproterozoic back-arc and arc-type magmatisms in the Rutong and Shiquanhe region, west of Tibet: Tectonic implications for the early-stage evolution of the Bangong-Nujiang suture zone and North Lhasa terrane - Xu Zhang; Di-Zhu Cai; Harald Furnes; Wei-Liang Liu; Rui Wang; Wei Li; Xing Liao; Chi Yan; Ru-Xin Ding; Yun Zhong (Precambrian Research, 2024)

CIP1, a CIPK23-interacting transporter, is implicated in Cd tolerance and phytoremediation - Jiayi Wang; Huihui Zhu; Ru’nan Huang; Jiming Xu; Li Huang; Jianli Yang; Weiwei Chen (Journal of Hazardous Materials, 2024)

Glutamate application maintains quality and antioxidant capacity of fresh-cut carrots by modulating GABA shunt, phenylpropanoid and ROS metabolism - Jinglin Zhang; Jing Zhao; Xiaoxia Zuo; Wanli You; Xueyin Ru; Feng Xu; Peng Jin; Yonghua Zheng; Shifeng Cao (Food Chemistry, 2024)

Dissolved oxygen and ammonia affect ammonia production via GDH/AMPK signaling pathway and alter flesh quality in Chinese perch (Siniperca chuatsi) - Ru Yang; Xuange Liu; Yong Liu; Qingda Tian; Ziwei Wang; Dejie Zhu; Zhisong Qian; Yi Yi; Jiacheng Hu; Yan Li; Xu-Fang Liang; Liwei Liu; et al. (Fish Physiology and Biochemistry, 2024)

Addition of α-ketoglutaric acid (AKG) reduces deamination in Chinese perch (Siniperca chuatsi) fed with fermented soybean meal as a substitute for fishmeal - Yufei Zhang; Jiacheng Hu; Peisong Lu; Ru Yang; Xu-Fang Liang; Liwei Liu (Fish Physiology and Biochemistry, 2024)

Nighttime warming and nitrogen addition effects on the microclimate of a freshwater wetland dominated by Phragmites australis - Yunpeng Guo; Jian Song; Jiayin Feng; Hongpeng Wang; Jinhua Zhang; Jingyi Ru; Xiaopan Wang; Xu Han; Huixia Ma; Yaru Lyu; Wenjing Ma; Chao Wang; et al. (Science of The Total Environment, 2024)

Positive association between chlorinated paraffins and the risk of allergic diseases in children and adolescents - Jing-Wen Huang; Ya-Ying Bai; Dao-Sen Wang; Wan-Ting He; Jing-Lin Zhang; Hai-Xin Tu; Jing-Yao Wang; Yun-Ting Zhang; Qi-Zhen Wu; Shu-Li Xu; He-Hai Huang; Mo Yang; et al. (Journal of Hazardous Materials, 2024)

Anhydride esterification to regulate water migration and reduce ice crystal formation in κ-carrageenan gel during freezing - Xinwei Xu; Feng Jiang; Kuncheng Lin; Jingjing Fang; Fuquan Chen; Yi Ru; Huifen Weng; Qiong Xiao; Qiuming Yang; Anfeng Xiao (Food Hydrocolloids, 2024)

Efficient removal of size-fractionated antibiotic resistance genes (ARGs) in WWTPs secondary effluent by vacuum ultraviolet (VUV) activated potassium peroxymonosulfate (PMS) - Xiao-Yan Fan; Shi-Long Xu; Xing Li; Zhi-Wei Zhou; Yu-Xi Gao; Jun-Ru Zhao; Zhong-Xing Zhang (Chemical Engineering Journal, 2024)

Toxicological evaluation and concentration of airborne PM0.1 in high air pollution period in Guangzhou, China - Mo Yang; Qi-Zhen Wu; Yun-Ting Zhang; Ari Leskinen; Xin-Feng Wang; Mika Komppula; Henri Hakkarainen; Marjut Roponen; Nan-Xiang Jin; Wei-Hong Tan; Shu-Li Xu; Li-Zi Lin; et al. (Science of The Total Environment, 2024)

Di (2-ethylhexyl) phthalate induced lipophagy-related renal ferroptosis in quail (Coturnix japonica) - Yu Zhu; Xiang-Yu Ma; Ling-Ge Cui; Ya-Ru Xu; Chen-Xi Li; Milton Talukder; Xue-Nan Li; Jin-Long Li (Science of The Total Environment, 2024)

Proteomics revealed composition- and size-related regulators for hepatic impairments induced by silica nanoparticles - Xinying Zhao; Ru Ma; Alimire Abulikemu; Yi Qi; Xiaoying Liu; Ji Wang; Kun Xu; Caixia Guo; Yanbo Li (Science of The Total Environment, 2024)

Construction of self-assembled nano cellulose crystals/chitosan nanobubbles composite hydrogel with improved gallic acid release property - Miral Javed; Hao Huang; Yueran Ma; Fatima-ezzahra Ettoumi; Lei Wang; Yanqun Xu; Hesham R. El-Seedi; Qiaomei Ru; Zisheng Luo (Food Chemistry, 2024)

Cultivating edible bio-inks: Elevating 3D printing with medium-internal-phase emulsion gel incorporating soybean protein isolate microgel particles - Jing-ru Song; Jia-rong Huang; Si-xu Ren; Hong-ze Zheng; Da-yong Zhou; Liang Song (Food Hydrocolloids, 2024)

Insights into the response of nitrogen metabolism to sulfamethoxazole contamination in constructed wetlands with varied substrates - Ya-Ru Zhang; Jia-Min Xu; Hao-Ran Xu; Guo-Dong Zhang; Xian-Bin Liu; Hao-Yi Cheng (Bioresource Technology, 2024)

Effect of Regional Brain Activity Following Repeat Transcranial Magnetic Stimulation in SCA3: A Secondary Analysis of a Randomized Clinical Trial - Xia Liu; Lin Zhang; Hao-Lin Xu; Xia-Hua Liu; Arif Sikandar; Meng-Cheng Li; Xiao-Yue Xia; Zi-Qiang Huang; Na-Ping Chen; Yu-Qing Tu; Jian-Ping Hu; Shi-Rui Gan; et al. (The Cerebellum, 2024)

Three new diterpenoids isolated from Euphorbia nematocypha Hand.-Mazz and their anti-fungal activity - Rong-Shuai Li; Zhi-Chang Xu; Ding-Mei Qin; Jia-Bi Huang; Meng-Ru Wang; Xue-Rong Zhao; Quan-Yu Yang; Wei-Lie Xiao; Rui-Rui Wang; Xiao-Li Li (Natural Product Research, 2024)

Subsurface organic amendment of a saline soil increases ecosystem multifunctionality and sunflower yield - Jiashen Song; Hongyuan Zhang; Fangdi Chang; Ru Yu; Jing Wang; Aiping Chen; Yang Xu; Yu Liu; Jie Zhou; Yuyi Li (Science of The Total Environment, 2024)

Calcium chloride treatment maintains quality and enhances antioxidant capacity of fresh-cut carrots through modulating DcCMLs-DcCAMTA3-mediated phenylpropanoid pathway - Jinglin Zhang; Xiaoxia Zuo; Yanfei Li; Xueyin Ru; Wanli You; Feng Xu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2024)

Tyrosine hydroxylase plays crucial roles in larval cuticle formation and larval-pupal tanning in the rice stem borer, Chilo suppressalis - Qing-Yu Xu; Zhi-Ling Zhang; Ru Zhang; Ary A. Hoffman; Ji-Chao Fang; Guang-Hua Luo (Pesticide Biochemistry and Physiology, 2024)

6PPD-quinone exposure induces neuronal mitochondrial dysfunction to exacerbate Lewy neurites formation induced by α-synuclein preformed fibrils seeding - Jiacheng Fang; Xiaoxiao Wang; Guodong Cao; Fuyue Wang; Yi Ru; Bolun Wang; Yanhao Zhang; Doudou Zhang; Jie Yan; Ji Xu; Jing Ji; Fenfen Ji; et al. (Journal of Hazardous Materials, 2024)

New insight into the bioaccumulation and trophic transfer of free and conjugated antibiotics in an estuarine food web based on multimedia fate and model simulation - Nian-Nian Wu; Shan Liu; Ru Xu; Qian-Yi Huang; Yun-Feng Pan; Heng-Xiang Li; Lang Lin; Rui Hou; Yuan-Yue Cheng; Xiang-Rong Xu (Journal of Hazardous Materials, 2024)

Study by means of 1H nuclear magnetic resonance of the oxidation process in high oleic sunflower oil and palm oil during deep-frying of fish cakes - Xiaoyu Luo; Benlun Hu; Caihua Jia; Ru Liu; Jianhua Rong; Siming Zhao; Meng Niu; Yan Xu; Tao Yin; Juan You (Food Research International, 2024)

Influence on the volatilization of ethyl esters: Nonnegligible role of long-chain fatty acids on Baijiu flavor via intermolecular interaction - Qing-Ru Liu; Xian-Li Lin; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Su-Yi Zhang; Cai-Hong Shen; Xiao-Juan Zhang; Zheng-Hong Xu (Food Chemistry, 2024)

Tea polyphenols alleviate TBBPA-induced inflammation, ferroptosis and apoptosis via TLR4/NF-κB pathway in carp gills - Ran Xu; Fu-xin Han; Hong-ru Wang; Jing-jing Wang; Zhao-long Cai; Meng-yao Guo (Fish & Shellfish Immunology, 2024)

Experimental and theoretical study on seismic behavior of a new UHPFRC sandwich wall and wall-wall joint - Ru-Rui Liu; Ran Ding; Yong-Tao Sun; Jian-Sheng Fan; Ding-Qiu Chen; Jian-Chao Xu (Engineering Structures, 2024)

Desynchronization of neural networks induced by transcranial magneto-acoustical stimulation: a modeling study - Zhenfang Ma; Yuhui Yang; Jianyang Xu; Yi Ru; Yu Yin (Neurophysiology, 2024)

Ratiometric G-quadruplex/hemin DNAzymes with low-dosage associative substrates - Rong Lai; Xingli Zeng; Qiuda Xu; Ying Xu; Xueni Li; Yulu Ru; Yilin Wang; Dandan Wang; Xiaoshun Zhou; Yong Shao (Analytica Chimica Acta, 2024)

Factors affecting the occurrence and accumulation of perfluoroalkyl acids in indoor dust in Tainan, Taiwan - Yi-Wei Biao; Jing-Ya Xu; Wan-Ru Chen (Chemosphere, 2024)

Silver nanoparticles induce endothelial cytotoxicity through ROS-mediated mitochondria-lysosome damage and autophagy perturbation: The protective role of N-acetylcysteine - Jing He; Yunyun Ma; Xudong Niu; Jiansheng Pei; Ru Yan; Fangjing Xu; Jing Ma; Xiaojuan Ma; Shaobin Jia; Wanrui Ma (Toxicology, 2024)

Density affects plant size in the Gobi Desert - Yonghua Li; Zhiming Xin; Bin Yao; Ruibing Duan; Xue Dong; Yanfeng Bao; Xinle Li; Yuan Ma; Yaru Huang; Fengmin Luo; Xing Li; Xu Wei; et al. (Science of The Total Environment, 2024)

Efficient electro-demulsification of O/W emulsions and simultaneous oil removal enabled by a multiscale porous biocarbon electrode - Kui Wang; Hailiang Zhao; Yingming Zhang; Xu Li; Mengyi Xu; Meirong Song; Guangxin Ru; Xiaolei Jiang; Xiuhong Zhu; Dandan Han; Yutao Dong; Kexin Shen; et al. (Chemical Engineering Journal, 2024)

Mechanism of enhanced microalgal biomass and lipid accumulation through symbiosis between a highly succinic acid-producing strain of Escherichia coli SUC and Aurantiochytrium sp. SW1 - Mei-Yu Zhang; Xin-Ru Xu; Ru-Ping Zhao; Chao Huang; Yuan-Da Song; Zi-Tong Zhao; Yu-Bin Zhao; Xiao-Jie Ren; Xin-He Zhao (Bioresource Technology, 2024)

Rapid detection of human adenovirus subgroup B using recombinase polymerase amplification assay - Yongzhe Zhu; Binghui Xia; Haizhou Xu; Zengxin Liu; Ru Wang; Qingqing Cai; Ping Zhao; Zhongtian Qi (Virus Genes, 2024)

Prenatal exposures to phthalates and bisphenols in relation to oxidative stress: single pollutant and mixtures analyses - Jia-Yue Zeng; Min Zhang; Xu-Hui Chen; Chong Liu; Yan-Ling Deng; Pan-Pan Chen; Yu Miao; Fei-Peng Cui; Tian Shi; Ting-Ting Lu; Xiao-Ying Liu; Yang Wu; et al. (Environmental Science and Pollution Research, 2024)

Metagenomic insights into the energy metabolism and immune variation of sea cucumber Apostichopus japonicus during reproduction - Beini Deng; Zhaoming Gao; Xiaoshang Ru; Haoyu Tong; Wenke Liang; Igor Eeckhaut; Libin Zhang; Jialei Xu (Aquaculture, 2024)

Transcriptomic analysis reveals the immune response mechanisms of sea cucumber Apostichopus japonicus under noise stress from offshore wind turbine - Xiaochen Cheng; Libin Zhang; Zhaoming Gao; Kehan Li; Jialei Xu; Weijian Liu; Xiaoshang Ru (Science of The Total Environment, 2024)

CaCl2 promoted phenolics accumulation via the CmCAMTA4-mediated transcriptional activation of phenylpropane pathway and energy metabolism in fresh-cut cantaloupe - Wanli You; Jinglin Zhang; Xueyin Ru; Feng Xu; Zhengguo Wu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2024)

Steroid metabolites as overlooked emerging contaminants: Insights from multimedia partitioning and source–sink simulation in an estuarine environment - Ru Xu; Shan Liu; Yun-Feng Pan; Nian-Nian Wu; Qian-Yi Huang; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu; Yuan-Yue Cheng (Journal of Hazardous Materials, 2024)

Tree ring oxygen isotope in Asia - Chenxi Xu; Ru Huang; Wenling An; Qingyu Zhao; Yaru Zhao; Junbo Ren; Yucheng Liu; Zhengtang Guo (Global and Planetary Change, 2024)

Effects of freezing methods on physicochemical properties, protein/fat oxidation and odor characteristics of surimi gels with different cross-linking degrees - Xiaoying Luo; Kang Huang; Yongxin Niu; Xu Zhang; Yueqi An; Ru Liu; Shanbai Xiong; Yang Hu (Food Chemistry, 2024)

Technological diversity in the tropical-subtropical zone of Southwest China during the terminal Pleistocene: excavations at Fodongdi Cave - Fa-Xiang Huan; Shi-Xia Yang; Feng Gao; Xin-Ying Zhou; Jian-Ping Yue; Yu-Xiu Zhang; Jin-Xu Wu; Qi-Jun Ruan; Kai-Wei Qiu; Jing-wen Xu; Nai-Ru Lin; Yi-Ren Wang; et al. (Archaeological and Anthropological Sciences, 2024)

Artificial light at night, MRI-based measures of brain iron deposition and incidence of multiple mental disorders - Jianbo Jin; Wenxing Han; Teng Yang; Zhihu Xu; Jin Zhang; Ru Cao; Yuxin Wang; Jiawei Wang; Xin Hu; Tiantian Gu; Fan He; Jing Huang; et al. (Science of The Total Environment, 2023)

Genome resources for the elite bread wheat cultivar Aikang 58 and mining of elite homeologous haplotypes for accelerating wheat improvement - Jizeng Jia; Guangyao Zhao; Danping Li; Kai Wang; Chuizheng Kong; Pingchuan Deng; Xueqing Yan; Xueyong Zhang; Zefu Lu; Shujuan Xu; Yuannian Jiao; Kang Chong; et al. (Molecular Plant, 2023)

Magmatic–hydrothermal evolution of the Koktokay No. 3 pegmatite, Altai, northwestern China: Constraints from in situ boron isotope and chemical compositions of tourmaline - Rong Yin; Xiao-Long Huang; Ru-Cheng Wang; Gang-Jian Wei; Yi-Gang Xu; Yu Wang; Xiao-Ming Sun; Le Zhang; Xiao-Ping Xia (Lithos, 2023)

Investigation on molecular characteristics of organic compounds during a full-scale landfill leachate treatment process based on non-targeted analysis - Ninghui Song; Qian Zhang; Yixuan Wang; Li Gao; Sitao Liu; Hao Yao; Ru Liu; Hang Xu (Environmental Research, 2023)

Wood frame structured carbons with integrated sieving layer for propylene/propane separation - Cheng-Tong Wang; Wen-Cui Li; Shuang Xu; Ru-Shuai Liu; Guang-Ping Hao; An-Hui Lu (Chemical Engineering Journal, 2023)

Dietary soybean lecithin promoted growth performance and feeding in juvenile Chinese perch (Siniperca chuatsi) could be by optimizing glucolipid metabolism - Dongliang Wu; Di Peng; Xu-Fang Liang; Ruipeng Xie; Ming Zeng; Junliang Chen; Jie Lan; Ru Yang; Jiacheng Hu; Peisong Lu (Fish Physiology and Biochemistry, 2023)

Mechanisms of swelling inhibition and seepage promotion of weathered crust elution-deposited rare earth ore by hydroxypropyl methyl cellulose - Aoyang Sha; Huifang Yang; Zhengyan He; Qin Zuo; Zhigao Xu; Chenjie Wu; Ming Wu; Ru'an Chi (Minerals Engineering, 2023)

Climate co-benefits of VOC control policies in China based on a cross-scale approach - Wen-Wen Zhang; Basil Sharp; Yu Gu; Shi-Chun Xu; Jianyun Nie; Ru-Yin Long; Mei-Fen Wu (Journal of Environmental Management, 2023)

Cyclodextrin-based metal-organic framework materials: Classifications, synthesis strategies and applications in variegated delivery systems - Ru-nan Zhao; Bei-wei Zhu; Yu Xu; Song-feng Yu; Wen-jun Wang; Dong-hong Liu; Jiang-ning Hu (Carbohydrate Polymers, 2023)

Mitogenome analysis reveals predominantly ancient Yellow River origin of population inhabiting Datong agro-pastoral ecotone along Great Wall - Yuqing Yan; Panxin Du; Jihong Zhang; Ruilan Li; Haoquan Bao; Qingli Fang; Ye Gao; Hailiang Meng; Yiran Xu; Haochen Shi; Hailong Yan; Xin Chang; et al. (Molecular Genetics and Genomics, 2023)

Paternal lipopolysaccharide exposure induced intrauterine growth restriction via the inactivation of placental MEST/PI3K/AKT pathway in mice - Pei-Ying Jiang; Shuai Lin; Jie-Ru Liu; Yan Liu; Li-Ming Zheng; Qiang Hong; Yi-Jun Fan; De-Xiang Xu; Yuan-Hua Chen (Archives of Toxicology, 2023)

YOLACTFusion: An instance segmentation method for RGB-NIR multimodal image fusion based on an attention mechanism - Cheng Liu; Qingchun Feng; Yuhuan Sun; Yajun Li; Mengfei Ru; Lijia Xu (Computers and Electronics in Agriculture, 2023)

A combined proteomics and metabolomics analysis reveals the invisible regulation of plant root responses to oxybenzone (benzophenone-3) stress - Shuhao Li; Shengxiang Ran; Craig A. Downs; Ru Xu; Qingming Li; Xin Zhong; Fenglin Zhong (Science of The Total Environment, 2023)

The interaction between DcCaM7 and DcCAMTA6 promotes γ-aminobutyric acid (GABA) accumulation via regulating GABA shunt in fresh-cut carrots - Jinglin Zhang; Yanfei Li; Xiaoxia Zuo; Xueyin Ru; Wanli You; Feng Xu; Peng Jin; Yonghua Zheng; Shifeng Cao (Postharvest Biology and Technology, 2023)

Ozone exposure associates with sperm quality indicators: Sperm telomere length as a potential mediating factor - Zhong-Hua Lu; Bin Sun; Yi-Xin Wang; Ya-Ru Wu; Yu-Jie Chen; Sheng-Zhi Sun; Shi-Jia Liang; Song Xu; Hao Chang; Heng-Gui Chen; Jie Zhang (Journal of Hazardous Materials, 2023)

Enhanced encapsulation of lutein using soy protein isolate nanoparticles prepared by pulsed electric field and pH shifting treatment - Rui Wang; Man-Qin Zeng; Yu-Wei Wu; Yong-Xin Teng; Lang-Hong Wang; Jian Li; Fei-Yue Xu; Bo-Ru Chen; Zhong Han; Xin-An Zeng (Food Chemistry, 2023)

A life-threatening bleeding prediction model for immune thrombocytopenia based on personalized machine learning: a nationwide prospective cohort study - Zhuo-Yu An; Ye-Jun Wu; Yu Hou; Heng Mei; Wei-Xia Nong; Wen-Qian Li; Hu Zhou; Ru Feng; Jian-Ping Shen; Jun Peng; Hai Zhou; Yi Liu; et al. (Science Bulletin, 2023)

Isolation and identification of 3,4-seco-labdane diterpenoids from Callicarpa nudiflora and investigation of their cytotoxicity against HepG2 cells - Qian-Qian Chen; Ming-Hui Fan; Hong-Tao Xu; Le-Yi Huang; Jin-Ling Liu; Shan-Shan Zhang; Ru-Ru Wang; Xiao-Hui Wei; Gui-Xin Chou (Phytochemistry, 2023)

Metabolomic profiling of Panax ginseng in response to Fusarium solani infection - Guijia Zhao; Shuyang Xing; Yang Wang; Xu Yang; Ru Sun; Lin Feng; Jifeng Wang; Tianxia Sun; Wenhui Lian; Yu Zhao (Physiological and Molecular Plant Pathology, 2023)

Application of self-organizing maps to coal elemental data - Na Xu; Wei Zhu; Ru Wang; Qiang Li; Zhiwei Wang; Robert B. Finkelman (International Journal of Coal Geology, 2023)

Impact of National Industrial Relocation Demonstration Zones (NIRDZs) policy on urban carbon emissions in China - Ke-Liang Wang; Ru-Yu Xu; Wei Jiang; Yuan Liu (Environmental Impact Assessment Review, 2023)

Enhanced catalytic nitrophenol reduction via highly porous hollow silica nanospheres stabilized Au nanoclusters - Ru Hu; Rui Xu; Zizhu Wang; Junyou Wang; Shenghu Zhou (Chemical Engineering Journal, 2023)

Age- and gender-related dispersion of brain networks across the lifespan - Qing Wang; Lingyu Qi; Cancan He; Haixia Feng; Chunming Xie; Chao-Gan Yan; Xiao Chen; Le Li; Francisco Xavier Castellanos; Tong-Jian Bai; Ning-Xuan Chen; Wei Chen; et al. (GeroScience, 2023)

Strategy for cost-effective BMPs of non-point source pollution in the small agricultural watershed of Poyang Lake: A case study of the Zhuxi River - Wei Liu; Lei Zhang; Huoliang Wu; Yinfeng Wang; Yalan Zhang; Jinying Xu; Dongyang Wei; Ru Zhang; Ying Yu; Daishe Wu; Xianchuan Xie (Chemosphere, 2023)

Leucine to tryptophane substitution in the pore helix IIP1 confer sodium channel resistance to pyrethroids and DDT - Huiming Wu; Jiali Qian; Zhanyi Xu; Ru Yan; Guonian Zhu; Shaoying Wu; Mengli Chen (Pesticide Biochemistry and Physiology, 2023)

Au@BN-enhanced laser desorption/ionization mass spectrometry and imaging for determination of fipronil and its metabolites in food and biological samples - Yanfang Zhao; Rabah Boukherroub; Guiju Xu; Huijuan Li; Ru-Song Zhao; Qin Wei; Xiang Yu; Xiangfeng Chen (Food Chemistry, 2023)

Effect of liver metastasis on the efficacy of immune checkpoint inhibitors in cancer patients: a systemic review and meta-analysis - Bao-Wen Tian; Cheng-Long Han; Han-Chao Wang; Lun-Jie Yan; Zi-Niu Ding; Hui Liu; Xin-Cheng Mao; Jin-Cheng Tian; Jun-Shuai Xue; Long-Shan Yang; Si-Yu Tan; Zhao-Ru Dong; et al. (Clinical & Experimental Metastasis, 2023)

Role of phosphite in the environmental phosphorus cycle - Wei Liu; Yalan Zhang; Mengqin Yu; Jinying Xu; Hu Du; Ru Zhang; Daishe Wu; Xianchuan Xie (Science of The Total Environment, 2023)

Gestational 1-nitropyrene exposure causes anxiety-like behavior partially by altering hippocampal epigenetic reprogramming of synaptic plasticity in male adult offspring - Bo Wang; Ting Zhao; Xiao-Xi Chen; Yan-Yan Zhu; Xue Lu; Qing-Hua Qian; Hui-Ru Chen; Xiu-Hong Meng; Hua Wang; Wei Wei; De-Xiang Xu (Journal of Hazardous Materials, 2023)

Genetic variation reveals the enhanced microbial hyaluronan biosynthesis via atmospheric and room temperature plasma - Zhi-Yuan Yao; Jin-Song Gong; Yu-Ru Liu; Jia-Yu Jiang; Yue-Sheng Zhang; Chang Su; Heng Li; Chuan-Li Kang; Lei Liu; Zheng-Hong Xu; Jin-Song Shi (Carbohydrate Polymers, 2023)

Exosomal MiR-381 from M2-polarized macrophages attenuates urethral fibroblasts activation through YAP/GLS1-regulated glutaminolysis - Ye-Hui Chen; Yi-Cheng Xu; Ting-Ting Lin; Hang Chen; Ru-Nan Dong; Feng-Ping Cai; Zhi-Bin Ke; Jia-Yin Chen; Yong Wei; Qing-Shui Zheng; Xue-Yi Xue; Ning Xu (Inflammation Research, 2023)

Calcination treatment of CoFe-layered double hydroxide enables enhanced chemodynamic and photothermal effects for antibacterial and antitumor applications - Ru Xu; Dongdong Zhang; Shuhan Chen; Jiajun Qiu; Xuanyong Liu (Applied Clay Science, 2023)

Prediction of higher heating value of coal based on gradient boosting regression tree model - Na Xu; Zhiwei Wang; Yuchen Dai; Qiang Li; Wei Zhu; Ru Wang; Robert B. Finkelman (International Journal of Coal Geology, 2023)

Effects of microbial transglutaminase on the gelling property and in vitro digestibility of fish scale gelatin from grass carp - Yonggang Chen; Yuhang Wang; Ru Liu; Shanbai Xiong; Yan Xu; Yang Hu (Food Bioscience, 2023)

An effective tool for tracking steroids and their metabolites at the watershed level: Combining fugacity modeling and a chemical indicator - Ru Xu; Shan Liu; Hui Chen; Qin-Wei Hao; Yong-Xia Hu; Heng-Xiang Li; Lang Lin; Rui Hou; Bing Hong; Shen Yu; Xiang-Rong Xu (Environmental Pollution, 2023)

Polybenzimidazole-reinforced polyethylene oxide-based polymer-in-salt electrolytes enabling excellent structural stability and superior electrochemical performance for lithium metal batteries - Lei Zou; Kun Shi; Honglei Liu; Yong Wu; Tao Xu; Qiang Wang; Zhangxian Chen; Zeheng Yang; Ru Song; Jianhui Su; Weixin Zhang (Chemical Engineering Journal, 2023)

Free and conjugated forms of metabolites are indispensable components of steroids: The first evidence from an estuarine food web - Shan Liu; Ru Xu; Yun-Feng Pan; Qian-Yi Huang; Nian-Nian Wu; Heng-Xiang Li; Lang Lin; Rui Hou; Xiang-Rong Xu (Water Research, 2023)

Dissolved biochar fractions and solid biochar particles inhibit soil acidification induced by nitrification through different mechanisms - Ren-Yong Shi; Ni Ni; Ru-Hai Wang; Jackson Nkoh Nkoh; Xiao-Ying Pan; Ge Dong; Ren-Kou Xu; Xiu-Min Cui; Jiu-Yu Li (Science of The Total Environment, 2023)

Metabolomics for in situ monitoring of attached Crassostrea gigas and Mytilus edulis: Effects of offshore wind farms on aquatic organisms - Ting Wang; Zhaoming Gao; Xiaoshang Ru; Xu Wang; Bo Yang; Libin Zhang (Marine Environmental Research, 2023)

Machine learning based age-authentication assisted by chemo-kinetics: Case study of strong-flavor Chinese Baijiu - Qing-Ru Liu; Xiao-Juan Zhang; Lei Zheng; Lian-Jun Meng; Guang-Qian Liu; Ting Yang; Zhen-Ming Lu; Li-Juan Chai; Song-Tao Wang; Jin-Song Shi; Cai-Hong Shen; Zheng-Hong Xu (Food Research International, 2023)

Atmospheric solids analysis probe-mass spectrometry (ASAP-MS) as a rapid fingerprinting technique to differentiate the harvest seasons of Tieguanyin oolong teas - Hui Ru Tan; Li Yan Chan; Adabelle Ong; Yong-Quan Xu; Xue-Bo Zhang; Weibiao Zhou (Food Chemistry, 2023)

Cadmium aggravates the blood-brain barrier disruption via inhibition of the Wnt7A/β-catenin signaling axis - Chen-Xi Li; Milton Talukder; Ya-Ru Xu; Shi-Yong Zhu; Ying-Xin Zhao; Jin-Long Li (Environmental Pollution, 2023)

Flexible, biocompatible, degradable silk fibroin based display - Zijie Xu; Zhi He; Jiani Huang; Wu Qiu; Leo N.Y. Cao; Aniruddha Patil; Bo-Ru Yang; Xiang Yang Liu; Wenxi Guo (Chemical Engineering Journal, 2023)

QTL-seq and transcriptomic integrative analyses reveal two positively regulated genes that control the low-temperature germination ability of MTP–maize introgression lines - Ru-Yu He; Jun-Jun Zheng; Yu Chen; Ze-Yang Pan; Tao Yang; Yang Zhou; Xiao-Feng Li; Xinyi Nan; Ying-Zheng Li; Ming-Jun Cheng; Yan Li; Yang Li; et al. (Theoretical and Applied Genetics, 2023)

Methylated Chromenoquinoline as a Novel Nucleus Fluorescent Probe for Nucleic Acid Imaging - Zhi-Hao Zhang; Qing Yu; Gang Zhang; Hai-Yan Peng; Ru Sun; Yu-Jie Xu; Jian-Feng Ge (Journal of Fluorescence, 2023)

A Cre knockin mouse reveals specific expression of Agouti gene in mesenchymal lineage cells in multiple organs and provides a unique tool for conditional gene targeting - Xing-Ru Shen; He-Li Zhang; Xu-Bo Zhao; Yang-Ge Wang; Xiao-Yang Tan; Lipeng Gao; Ruilin Sun; Xin-Hua Liao (Transgenic Research, 2023)

Sources, chemical components, and toxicological responses of size segregated urban air PM samples in high air pollution season in Guangzhou, China - Mo Yang; Hui-Xian Zeng; Xin-Feng Wang; Henri Hakkarainen; Ari Leskinen; Mika Komppula; Marjut Roponen; Qi-Zhen Wu; Shu-Li Xu; Li-Zi Lin; Ru-Qing Liu; Li-Wen Hu; et al. (Science of The Total Environment, 2023)

Direct emissions of particulate glyoxal and methylglyoxal from biomass burning and coal combustion - Ting Wang; Ru-Jin Huang; Lu Yang; Wenting Dai; Haiyan Ni; Yuquan Gong; Jie Guo; Haobin Zhong; Chunshui Lin; Wei Xu (Science of The Total Environment, 2023)

Olefin-linked cationic covalent organic frameworks for efficient extraction of ReO4−/99TcO4− - Wei-Rong Cui; Wei Xu; Yi-Ru Chen; Kai Liu; Wei-Bin Qiu; Yibao Li; Jian-Ding Qiu (Journal of Hazardous Materials, 2023)

Constructing redox-active 3D covalent organic frameworks with high-affinity hexameric binding sites for enhanced uranium capture - Yi-Ru Chen; Xiu Wang; Wei Xu; Kai Liu; Wei-Bin Qiu; Yongquan Wu; Yibao Li; Wei-Rong Cui (Chemical Engineering Journal, 2023)

Inhibition of perilipin 2 attenuates cerebral ischemia/reperfusion injury by blocking NLRP3 inflammasome activation both in vivo and in vitro - Xu-Ying Liu; Qiu-Shi Li; Wen-Hai Yang; Yue Qiu; Fei-Fei Zhang; Xiu-Hui Mei; Qi-Wen Yuan; Ru-Bo Sui (In Vitro Cellular & Developmental Biology - Animal, 2023)

Can technological finance cooperation pilot policy improve energy efficiency? Evidence from a quasi-experiment in China - Bin Zhao; Ru-Yu Xu (Environmental Science and Pollution Research, 2023)

Restrictions on Niobium enrichment by alteration of Niobium-rich biotite in pure water, acid, alkaline and fluoride-bearing solutions at 200 MPa and 300–600 °C - Zhao-Yu Yang; Ru-Cheng Wang; Xu-Dong Che; Daniel Harlov (Geochimica et Cosmochimica Acta, 2023)

Effects of polystyrene nanoplastics on the physiological and biochemical characteristics of microalga Scenedesmus quadricauda - Ru-ru Li; Bin-liang Wang; Fang-ru Nan; Jun-ping Lv; Xu-dong Liu; Qi Liu; Jia Feng; Shu-lian Xie (Environmental Pollution, 2023)

Precision nitrogen management regimes to obtain high yield and good eating quality of medium indica hybrid rice in mechanical transplanting with bowl-type nursery tray (MTB) based on the critical nitrogen concentration - Haibing He; Kun Yang; Haochong Xu; Bo Yao; Ganghua Li; Xuenan Zhang; Ru Yang; Cuicui You; Jian Ke; Liquan Wu (European Journal of Agronomy, 2023)

Contribution of Tibetan Plateau ecosystems to local and remote precipitation through moisture recycling - Yan Li; Ru Xu; Kun Yang; Yanxu Liu; Shuai Wang; Sha Zhou; Zhao Yang; Xiaoming Feng; Chunyang He; Zhengjie Xu; Wenwu Zhao (Global Change Biology, 2023)
The ecosystems of the Tibetan Plateau (TP) provide multiple important ecosystem services that benefit both local populations and those beyond, such as through climate regulation services on precipitation for East Asia and China. However, the precipitation regulation service of the TP ecosystems for supplying moisture and maintaining precipitation is yet to be evaluated. In this study, we used the moisture recycling framework and a moisture tracking model to quantify the precipitation regulation services of TP ecosystems for their contribution to precipitation. We found TP ecosystems contributed substantially to local and downwind precipitation, with a contribution of 221 mm/year for the TP and neighboring areas through evapotranspiration (ET) (104 mm/year through transpiration), declined to

Fiscal decentralization, industrial structure upgrading, and carbon emissions: evidence from China - Bin Zhao; Ke-Liang Wang; Ru-Yu Xu (Environmental Science and Pollution Research, 2023)

Ultrastructure and distribution of antennal sensilla of Bombus terrestris (Hymenoptera: Apidae) - Xi Huang; Xi-lian Xu; Ru-xu Li; Su Wang; Li-xia Tian (Zoologischer Anzeiger, 2023)

Proteomic profiling reveals dysregulated mitochondrial complex subunits responsible for myocardial toxicity induced by SiNPs - Xinying Zhao; Hailin Xu; Yan Li; Ru Ma; Yi Qi; Min Zhang; Caixia Guo; Zhiwei Sun; Yanbo Li (Science of The Total Environment, 2023)

Evidence that offshore wind farms might affect marine sediment quality and microbial communities - Ting Wang; Xiaoshang Ru; Beini Deng; Chenxi Zhang; Xu Wang; Bo Yang; Libin Zhang (Science of The Total Environment, 2023)

Metallurgical performance and structural characteristics of cokes of hypercoal prepared from the mixture of low-rank coal and biomass residue - Jun Zhao; Hong Liu; Haochen Zhang; Xiaolin Song; Haibin Zuo; Guangwei Wang; Zhigao Xu; Ming Wu; Zhenyue Zhang; Ru'an Chi (Fuel, 2023)

Taking glucose as intermediate bridge-signal-molecule for on-site and convenient detection of ochratoxin A in rice with portable glucose meter - Ru Zhang; Chao Yan; Ziwen Zong; Wei Qu; Li Yao; Jianguo Xu; Yingyue Zhu; Bangben Yao; Wei Chen (Food Chemistry, 2023)

Combination of pulsed electric field and pH shifting improves the solubility, emulsifying, foaming of commercial soy protein isolate - Rui Wang; Lang-Hong Wang; Qing-Hui Wen; Fei He; Fei-Yue Xu; Bo-Ru Chen; Xin-An Zeng (Food Hydrocolloids, 2023)

Association between long-term ambient ozone exposure and attention-deficit/hyperactivity disorder symptoms among Chinese children - Peien Zhou; Wangjian Zhang; Yu-Jie Xu; Ru-Qing Liu; Zhengmin Qian; Stephen Edward McMillin; Elizabeth Bingheim; Li-Zi Lin; Xiao-Wen Zeng; Bo-Yi Yang; Li-Wen Hu; Wen Chen; et al. (Environmental Research, 2023)

Air pollution, greenness and risk of overweight among middle-aged and older adults: A cohort study in China - Wenxing Han; Zhihu Xu; Xin Hu; Ru Cao; Yuxin Wang; Jianbo Jin; Jiawei Wang; Teng Yang; Qiang Zeng; Jing Huang; Guoxing Li (Environmental Research, 2023)

Three-dimensional hydroxylated covalent organic frameworks for solid phase extraction of glucocorticoids in environmental water samples - Chuqing Liu; Guiju Xu; Baoyu Li; Xiaoli Wang; Jin-Ming Lin; Ru-Song Zhao (Analytica Chimica Acta, 2023)

A Bounded Near-Bottom Cruise Trajectory Planning Algorithm for Underwater Vehicles - Jingyu Ru; Han Yu; Hao Liu; Jiayuan Liu; Xiangyue Zhang; Hongli Xu (Journal of Marine Science and Engineering, 2022)
The trajectory planning algorithm of underwater vehicle near-bottom cruise is important to scientific investigation, industrial inspection, and military affairs. An autonomous underwater vehicle (AUV) often faces the problems of complex underwater environment and large cruise area in a real environment, and some robots must hide themselves during the cruise. However, to the best of our knowledge, few studies have focused on trajectory planning algorithms for AUVs with multiple constraints on large-scale maps. The currently used algorithms are not effective at solving length-constraint problems, and the mainstream trajectory planning algorithms for robots cannot be directly applied to the needs of underwater vehicle sailing near the bottom. Therefore, we present a bounded ridge-based trajectory planning algorithm (RA*) for an AUV to go on a near-bottom cruise. In the algorithm, we design a safety map based on a spherical structure to ensure the safe operation of the robot. In addressing the length-constraint problem and large-scale map planning problem, this paper proposes a two-stage framework for RA*, which designs map compression and parallel computation using a coarse-fine planning framework to solve the large-scale trajectory planning problem and uses a bounded search method to meet the trajectory planning requirements of length constraint. In this study, experiments based on the virtual ocean ridge are conducted, and the results validate the effectiveness and efficiency of the proposed RA* with MCPC algorithm framework.

Nitrogen enrichment alters multiple dimensions of grassland functional stability via changing compositional stability - Qianna Xu; Xian Yang; Jian Song; Jingyi Ru; Jianyang Xia; Shaopeng Wang; Shiqiang Wan; Lin Jiang (Ecology Letters, 2022)
Anthropogenic nutrient enrichment is known to alter the composition and functioning of plant communities. However, how nutrient enrichment influences multiple dimensions of community‐ and ecosystem‐level stability remains poorly understood. Using data from a nitrogen (N) and phosphorus (P) addition experiment in a temperate semi‐arid grassland that experienced a natural drought, we show that N enrichment, not P enrichment, decreased grassland functional and compositional temporal stability, resistance and recovery but increased functional and compositional resilience. Compositional stability and species asynchrony, rather than species diversity, were identified as key determinants of all dimensions of grassland functional stability, except for recovery. Whereas grassland functional recovery was decoupled from compositional recovery, N enrichment altered other dimensions of functional stability primarily through changing their corresponding compositional stability dimensions. Our findings highlight the need to examine ecological stability at the community level for a more mechanistic understanding of ecosystem dynamics in the face of environmental change.

Recent advances in biotechnological production of polyunsaturated fatty acids by Yarrowia lipolytica - Yu-Lei Jia; Ling-Ru Wang; Zi-Xu Zhang; Yang Gu; Xiao-Man Sun (Critical Reviews in Food Science and Nutrition, 2022)

Physiological responses of marine Chlorella sp. exposed to environmental levels of triphenyltin - Zhihan Cao; Ping Li; Jinchuang Ru; Xuqian Cao; Xu Wang; Bin Liu; Zhi-Hua Li (Environmental Science and Pollution Research, 2022)

The impact of low-carbon city pilot policy on green total-factor productivity in China’s cities - Ke-Liang Wang; Jin Li; Ru-Yu Xu; Su-Qin Pang; Zhuang Miao; Hua-Ping Sun (Environmental Science and Pollution Research, 2022)

Progressive Failure Characterization of Sandstone from Yingjinshan Area in Qinghai-Tibet Plateau - Xinzhong Wang; Heping Xie; Ru Zhang; Guangze Zhang; Zhengxuan Xu; Jianhui Deng; Dong Wang; Cunbao Li; Gan Feng; Zetian Zhang; Li Ren (Rock Mechanics and Rock Engineering, 2022)

Bio-electrocatalytic degradation of tetracycline by stainless-steel mesh based molybdenum carbide electrode - Zhi-Hao Zhang; Jia-Ying Xu; Tao Li; Shi-Ru Gao; Xiao-Li Yang (Environmental Science and Pollution Research, 2022)

Insights into the development of pentylenetetrazole-induced epileptic seizures from dynamic metabolomic changes - Xue Zhao; Peixuan Cheng; Ru Xu; Kaili Meng; Sha Liao; Pu Jia; Xiaohui Zheng; Chaoni Xiao (Metabolic Brain Disease, 2022)

Irisin promotes the proliferation and tenogenic differentiation of rat tendon-derived stem/progenitor cells via activating YAP/TAZ - Langhai Xu; Zhonggai Chen; Tingting Geng; Bin Ru; Quan Wan; Jianbin Zhang; Shun Li; Wenjun Cai (In Vitro Cellular & Developmental Biology - Animal, 2022)
Tendinopathy is a common tendon disorder characterized by pain, swelling, and dysfunction. Current evidence has demonstrated that the depletion of stem cell pool and non-tenogenic differentiation of tendon-derived stem/progenitor cells (TSPCs) might account for the pathogenesis of tendinopathy. FNDC5/Irisin, as a novel exercise-induced myokine, is proved to be involved in the exercise-induced protective effects on musculoskeletal disorders. However, whether irisin can affect TSPCs fate is still unknown. To ascertain the roles of irisin on the proliferation and tenogenic differentiation of TSPCs, rat TSPCs were isolated and incubated with irisin. Cell viability, phenotypic changes, and related signaling pathways were evaluated by CCK-8 assay, colony formation assay, real-time PCR, Western blot, immunofluorescence, and proteasome activity assay. We found that irisin treatment increased the proliferative and colony-forming abilities, and promoted the tenogenic differentiation of TSPCs by upregulating the expression of YAP/TAZ. In conclusion, our work showed for the first time that irisin promotes the proliferation and tenogenic differentiation of rat TSPCs in vitro by activating YAP/TAZ, and the process was associated with a ubiquitin-proteasome proteolytic pathway. In conclusion, irisin and agents targeting YAP/TAZ may be promising therapeutic options for tendinopathy.

Strength and deformation behavior of columnar jointed rock masses under different confining pressures - Zhi-nan Lin; Hai-feng Long; Wei-ya Xu; Ru-bin Wang; Shi-hong Feng (Arabian Journal of Geosciences, 2022)

Phenomenon of the sediment deposition in a hydraulic jump region of open channels - Wei-lin Xu; Guo-guang Wang; Shi-hao Fu; Wang-ru Wei (Journal of Mountain Science, 2022)

Clinical efficacy of melatonin as adjunctive therapy to non-surgical treatment of periodontitis: a systematic review and meta-analysis - Ru-Yue Liu; Lin Li; Zhong-Ti Zhang; Ting Wu; Shuang Lin; Xu-Tong Zhang (Inflammopharmacology, 2022)

A new highly oxygenated germacranolide from Carpesium nepalense var. lanatum (C.B.Clarke) Kitam - Yi-Fan Yu; Yue-Qian Li; Ru-Yue Wang; Xu Liu; Wen-Bo Cui; Xiao-Han Chen; Cheng-Mu Zhao; Feng-Ming Qi; Zhan-Xin Zhang; Dong-Qing Fei (Natural Product Research, 2022)

Land development suitability analysis for transport planning evaluation and optimization in mountainous ecological region - Gao-ru Zhu; Man Wang; Qi-li Li; Jie Liu; Yan-ni Zhao; Jia-wei Gao; Hong-lei Xu (Journal of Mountain Science, 2022)

Complete genome sequencing and evolutionary analysis of hepatitis C virus subtype 6a, including strains from Guangdong Province, China - Ru Xu; Hao Wang; Jieting Huang; Min Wang; Qiao Liao; Zhengang Shan; Huishan Zhong; Xia Rong; Yongshui Fu (Archives of Virology, 2022)

Soil moisture response to land use and topography across a semi-arid watershed: Implications for vegetation restoration on the Chinese Loess Plateau - Lu Xia; Ru-tian Bi; Xiao-yu Song; Wei Hu; Chun-juan Lyu; Xu Xi; Huai-you Li (Journal of Mountain Science, 2022)

Correction to: Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

A Multi-AUV Path Planning System Based on the Omni-Directional Sensing Ability - Jingyu Ru; Shuangjiang Yu; Hao Wu; Yuhan Li; Chengdong Wu; Zixi Jia; Hongli Xu (Journal of Marine Science and Engineering, 2021)
Following the development of autonomous underwater vehicles (AUVs), multiple trajectory-based submarine target information collection constitutes one of the key technologies that significantly influence underwater information collection ability and deployment efficiency. In this paper, we propose an underwater information collection AUV, O-AUV, that can perceive the omnidirectional area and could detect a larger area than the traditional AUV. A 3D sensing model for the O-AUV is proposed to describe the complex underwater information collection spaces. Thereafter, a cube-based environment model involving candidate observation point calculation methods are suggested to adapt the O-AUV model. A voyage cost map is also built according to the multi-AUV path planning for a common submarine mission that must traverse numerous mission targets in complex environments through the R-Dijkstra algorithm. Specifically, the voyage planning problem is solved through a critical algorithm called ANSGA (accelerated NSGA-II algorithm), which in turn, is developed by modifying the non-dominated sorting genetic algorithm (NSGA-II) to accelerate the optimization rate for the Pareto solution. Experiments are carried out in MATLAB, and the results verify the validity of the proposed O-AUV+ANSGA algorithm framework.

Transcriptome analysis of differentially expressed genes in chrysanthemum MET1 RNA interference lines - Dong-ru Kang; Yi Zhu; Shuai-lei Li; Peng-hui Ai; Muhammad Ayoub Khan; Hong-xu Ding; Ying Wang; Zi-cheng Wang (Physiology and Molecular Biology of Plants, 2021)

Inhibitory effects of aloperine on voltage-gated Na+ channels in rat ventricular myocytes - Meng-ting Li; Ya-ya Du; Fei Zhong; Jie-ru Wang; You-wei Gu; Yue Zhang; Xuan-tong Huang; Yi-zhou Deng; Zheng-xin Xu (Naunyn-Schmiedeberg's Archives of Pharmacology, 2021)

Magnolol attenuates inflammatory pain by inhibiting sodium currents in mouse dorsal root ganglion neurons - Lu-lu Zhang; Jie Qiu; Jiang-ru Hong; Xiu-qi Xu; Guang-qin Zhang; Guang Li (Inflammopharmacology, 2021)

Molecular epidemiological characteristics of echovirus 6 in mainland China: extensive circulation of genotype F from 2007 to 2018 - Wenjun Cheng; Tianjiao Ji; Shuaifeng Zhou; Yong Shi; Lili Jiang; Yong Zhang; Dongmei Yan; Qian Yang; Yang Song; Ru Cai; Wenbo Xu (Archives of Virology, 2021)
Echovirus 6 (E6) is associated with various clinical diseases and is frequently detected in environmental sewage. Despite its high prevalence in humans and the environment, little is known about its molecular phylogeography in mainland China. In this study, 114 of 21,539 (0.53%) clinical specimens from hand, foot, and mouth disease (HFMD) cases collected between 2007 and 2018 were positive for E6. The complete VP1 sequences of 87 representative E6 strains, including 24 strains from this study, were used to investigate the evolutionary genetic characteristics and geographical spread of E6 strains. Phylogenetic analysis based on VP1 nucleotide sequence divergence showed that, globally, E6 strains can be grouped into six genotypes, designated A to F. Chinese E6 strains collected between 1988 and 2018 were found to belong to genotypes C, E, and F, with genotype F being predominant from 2007 to 2018. There was no significant difference in the geographical distribution of each genotype. The evolutionary rate of E6 was estimated to be 3.631 × 10 -3 substitutions site -1 year -1 (95% highest posterior density [HPD]: 3.2406 × 10 -3 -4.031 × 10 -3 substitutions site -1 year -1 ) by Bayesian MCMC analysis. The most recent common ancestor of the E6 genotypes was traced back to 1863, whereas their common ancestor in China was traced back to around 1962. A small genetic shift was detected in the Chinese E6 population size in 2009 according to Bayesian skyline analysis, which indicated that there might have been an epidemic around that year.

Selective Ferroptosis Inhibitor Liproxstatin-1 Attenuates Neurological Deficits and Neuroinflammation After Subarachnoid Hemorrhage - Yang Cao; Yin Li; Chao He; Feng Yan; Jian-Ru Li; Hang-Zhe Xu; Jian-Feng Zhuang; Hang Zhou; Yu-Cong Peng; Xiong-Jie Fu; Xiao-Yang Lu; Yuan Yao; et al. (Neuroscience Bulletin, 2021)

Alkaloids and phenylpropanoid from Rhizomes of Arundo donax L - Qing-Ru Liu; Juan Li; Xiao-Fang Zhao; Bo Xu; Xing-Hua Xiao; Jie Ren; Shun-Xiang Li (Natural Product Research, 2021)

TRIP13 promotes the proliferation and invasion of lung cancer cells via the Wnt signaling pathway and epithelial–mesenchymal transition - Zhi-Han Li; Lei Lei; Liang-Ru Fei; Wen-Jing Huang; Yi-Wen Zheng; Mai-Qing Yang; Zhao Wang; Chen-Chen Liu; Hong-Tao Xu (Journal of Molecular Histology, 2021)

Functional connectivity changes of nucleus Accumbens Shell portion in left mesial temporal lobe epilepsy patients - Ru Yang; Xixi Zhao; Jun Liu; Xufeng Yao; Feng Hou; Yikai Xu; Qianjin Feng (Brain Imaging and Behavior, 2020)

Rapid identification of landslide, collapse and crack based on low-altitude remote sensing image of UAV - Xu-gang Lian; Zou-jun Li; Hong-yan Yuan; Ji-bo Liu; Yan-jun Zhang; Xiao-yu Liu; Yan-ru Wu (Journal of Mountain Science, 2020)

Effects of Al stress on the growth and nitrogen uptake of maize varieties with different Al tolerance as related with Al chemical forms on root surfaces - Xiao-ying Pan; Ge Dong; Xian He; Ru-hai Wang; Ren-kou Xu; Ting-ting Mu (Journal of Soils and Sediments, 2020)

Low Serum Uric Acid Levels Promote Hypertensive Intracerebral Hemorrhage by Disrupting the Smooth Muscle Cell-Elastin Contractile Unit and Upregulating the Erk1/2-MMP Axis - Ning Xiao; Tian-long Liu; Hao Li; Hao-chen Xu; Jing Ge; Hong-yan Wen; Cong-xia Bai; Li Song; Ying-ying Sun; Yin-hui Zhang; Ru-tai Hui; Wei-hua Song; et al. (Translational Stroke Research, 2020)

Liquiritin inhibits proliferation and induces apoptosis in HepG2 hepatocellular carcinoma cells via the ROS-mediated MAPK/AKT/NF-κB signaling pathway - Jia-Ru Wang; Tian-Zhu Li; Cheng Wang; Shu-Mei Li; Ying-Hua Luo; Xian-Ji Piao; Yu-Chao Feng; Yi Zhang; Wan-Ting Xu; Yu Zhang; Tong Zhang; Shi-Nong Wang; et al. (Naunyn-Schmiedeberg's Archives of Pharmacology, 2020)

Distribution Characteristics of Rare Earth Elements and Selenium in Hair of Centenarians Living in China Longevity Region - Ru Zhang; Li Wang; Yonghua Li; Hairong Li; Yuefeng Xu (Biological Trace Element Research, 2020)

Corticosterone Induced the Increase of proBDNF in Primary Hippocampal Neurons Via Endoplasmic Reticulum Stress - Yu Liu; Guang-Jing Zou; Bo-Xuan Tu; Zhao-Lan Hu; Cong Luo; Yan-Hui Cui; Yang Xu; Fang Li; Ru-Ping Dai; Fang-Fang Bi; Chang-Qi Li (Neurotoxicity Research, 2020)

Prenatal di-(2-ethylhexyl) phthalate maternal exposure impairs the spatial memory of adult mouse offspring in a phase- and gender-dependent manner - Ling-Li Zhao; Ru Shen; Cong-Cong Sun; Shan-Yu Zhang; Bo Wang; Mei-Fang Sun; De-Xiang Xu (Environmental Science and Pollution Research, 2020)

Testing and constitutive modelling of the mechanical behaviours of gravelly soil material - Jiu-Chang Zhang; Yue Li; Bo Xu; Qin-Xiang Meng; Qiang Zhang; Ru-Bin Wang (Arabian Journal of Geosciences, 2020)

Enhanced Antitumor Efficacy of Curcumin-Loaded PLGA Nanoparticles Coated with Unique Fungal Hydrophobin - Lu Sun; Hui Xu; Jing-hua Xu; Shao-ning Wang; Jun-wei Wang; Hong-feng Zhang; Wei-ru Jia; Lin-sen Li (AAPS PharmSciTech, 2020)

Endophytic colonization by Beauveria bassiana increases the resistance of tomatoes against Bemisia tabaci - Qiu-Yang Wei; Ya-Ying Li; Chen Xu; Yi-Xia Wu; Ya-Ru Zhang; Huai Liu (Arthropod-Plant Interactions, 2020)
Beauveria bassiana , an entomopathogenic fungus, can exist asymptomatically as an endophyte in many plants. This study aimed to determine the efficiency of B. bassiana colonization of tomato plants using different inoculation methods, and how colonization of the host plant affects the key pest of tomato, the whitefly Bemisia tabaci . To confirm fungal colonization efficiency, nested PCR technique was used to detect B. bassiana sequences in Solanum lycopersicum . Distribution of the fungus within the plant parts was determined by selective medium. Tomato growth parameters were determined with plants that had been inoculated using direct spraying or irrigation of the rhizosphere. B. tabaci performance assays were carried out in a cage, and preference to treatments was determined using Y-tube olfactometer studies. Results show that B. bassiana can effectively colonize tomato, with colonization rate using leaf spraying reaching 100% within 14 days. Fungal presence was not uniformly distributed among plant parts, but was biased towards the inoculation sites. For inoculation, conidial suspension sprayed at 1 × 10 8 conidia/ml resulted in the highest number of isolated colonies in leaf tissue, 8.5 ± 2.02 colonies per 2 g of fresh tissue ( F 4,19 = 2.779, P = 0.045), and reached the lowest with root treatment. Although only small differences were observed among the growth indicators, leaf spray inoculation resulted in a significant positive influence on plant growth (PC1 55.7% contributions scores = 2.645) in further Principal component analysis. As for the feeding selectivity, B. tabaci preferred uninoculated plants. In Y-tube olfactometer assay, 80.5% of adults selected uninoculated plants. These findings add to the understanding of the interactions between B. bassiana and plants and indicate the potential of expanding the use of entomopathogenic fungi for crop protection.

Thioredoxin-Interacting Protein (TXNIP) Regulates Parkin/PINK1-mediated Mitophagy in Dopaminergic Neurons Under High-glucose Conditions: Implications for Molecular Links Between Parkinson’s Disease and Diabetes - Cun-Jin Su; Zhu Shen; Ru-Xiao Cui; Ya Huang; De-Lai Xu; Feng-Lun Zhao; Jie Pan; Ai-Ming Shi; Tong Liu; Yun-Li Yu (Neuroscience Bulletin, 2020)

Allopatric divergence and hybridization within Cupressus chengiana (Cupressaceae), a threatened conifer in the northern Hengduan Mountains of western China - Jialiang Li; Richard I. Milne; Dafu Ru; Jibin Miao; Wenjing Tao; Lei Zhang; Jingjing Xu; Jianquan Liu; Kangshan Mao (Molecular Ecology, 2020)
Having a comprehensive understanding of population structure, genetic differentiation and demographic history is important for the conservation and management of threatened species. High‐throughput sequencing (HTS) provides exciting opportunities to address a wide range of factors for conservation genetics. Here, we generated HTS data and identified 266,884 high‐quality single nucleotide polymorphisms from 82 individuals of Cupressus chengiana , to assess population genomics across the species' full range, comprising the Daduhe River (DDH), Minjiang River (MJR) and Bailongjiang River (BLJ) catchments in western China. admixture , principal components analysis and phylogenetic analyses indicated that each region contains a distinct lineage, with high levels of differentiation between them (DDH, MJR and BLJ lineages). MJR was newly distinguished compared to previous surveys, and evidence including coalescent simulations supported a hybrid origin of MJR during the Quaternary. Each of these three lineages should be recognized as an evolutionarily significant unit (ESU), due to isolation, differing genetic adaptations and different demographic history. Currently, each ESU faces distinct threats, and will require different conservation strategies. Our work shows that population genomic approaches using HTS can reconstruct the complex evolutionary history of threatened species in mountainous regions, and hence inform conservation efforts, and contribute to the understanding of high biodiversity in mountains.

Modified stepwise mini-incision microdissection testicular sperm extraction: a useful technique for patients with a history of orchidopexy affected by non-obstructive azoospermia - Peng Li; Chen-cheng Yao; Er-lei Zhi; Yuan Xu; Zhong Wan; Ying-chuan Jiang; Yu-hua Huang; Yue-hua Gong; Hui-xing Chen; Ru-hui Tian; Chao Yang; Liang-yu Zhao; et al. (Journal of Zhejiang University-SCIENCE B, 2020)

Three new labdane-type diterpenoids from Callicarpa macrophylla Vahl. - Zhen-Hui Wang; Huan-Jun Xu; Yang-Yang Zhai; Lan-Ping Yang; Qiang Li; Mei Huang; Xing-Ying Chen; Wen-Kui Zhang; Yue-Li Meng; Qing-Ling Zhang; Chao Niu; Yan-Ru Zhang (Natural Product Research, 2019)

Mechanical Analysis of Weakly Cemented Roof of Gob-side Entry Retaining in Fully-Mechanized Top Coal Caving Mining - Qingheng Gu; Wenkai Ru; Yunliang Tan; Jianguo Ning; Qiang Xu (Geotechnical and Geological Engineering, 2019)

Differential PCR detection of Streptococcus agalactiae and Streptococcus iniae in tilapia ( Oreochromis niloticus ) by a single primer pair - Miao Cui; Huijie Zhang; Jingjing Li; Ru Liu; Min Wu; Delin Xu; Qizhong Zhang (Journal of Fish Diseases, 2019)

Hepatitis C virus 3b strains in injection drug users in Guangdong Province, China, may have originated in Yunnan Province - Min Wang; Qiao Liao; Ru Xu; Dandan Song; Jieting Huang; Qingzhu You; Zhengang Shan; Ke Huang; Xia Rong; Yongshui Fu (Archives of Virology, 2019)

Identification and characterisation of a glycine-rich RNA-binding protein as an endogenous suppressor of RNA silencing from Nicotiana glutinosa - Xu Huang; Ru Yu; Wenjing Li; Liwei Geng; Xiuli Jing; Changxiang Zhu; Hongmei Liu (Planta, 2019)

Transplantation of UC-MSCs on collagen scaffold activates follicles in dormant ovaries of POF patients with long history of infertility - Lijun Ding; Guijun Yan; Bin Wang; Lu Xu; Yan Gu; Tong Ru; Xiaoying Cui; Lei Lei; Jingyu Liu; Xiaoqiang Sheng; Bin Wang; Chunxue Zhang; et al. (Science China Life Sciences, 2018)

Efficient generation of functional cardiomyocytes from human umbilical cord-derived virus-free induced pluripotent stem cells - Kai Hong Wu; Su Yun Wang; Qian Ru Xiao; Yu Yang; Ning Ping Huang; Xu Ming Mo; Jian Sun (Cell and Tissue Research, 2018)

Combined prednisone and levothyroxine improve treatment of severe thrombocytopenia in hepatitis B with compensatory cirrhosis accompanied by subclinical and overt hypothyroidism - Jing Xue; Ru Feng; Haixia Fu; Qian Jiang; Hao Jiang; Jing Lu; Hui Liu; Jingwen Wang; Ting Niu; Xin Wang; Yandi Xie; Hao Wang; et al. (Science China Life Sciences, 2018)

Aquatic plant debris changes sediment enzymatic activity and microbial community structure - Wan-Lei Xue; Wei Pan; Qi Lu; Qian-Ru Xu; Cai-Nan Wu; Shao-Ting Du (Environmental Science and Pollution Research, 2018)

Cadmium phytoextraction potential of king grass (Pennisetum sinese Roxb.) and responses of rhizosphere bacterial communities to a cadmium pollution gradient - Li Hu; Ru Wang; Xianglin Liu; Bo Xu; Tuanhui Xie; Yunyun Li; Mingkuang Wang; Guo Wang; Yanhui Chen (Environmental Science and Pollution Research, 2018)

EGCG : Potential application as a protective agent against grass carp reovirus in aquaculture - H Wang; Yq Chen; Gm Ru; Yq Xu; Lq Lu (Journal of Fish Diseases, 2018)
Grass carp reovirus ( GCRV ) is the primary cause of grass carp haemorrhagic disease. The major catechin in green tea, (–)‐epigallocatechin‐3‐gallate ( EGCG ), has been found to have anti‐ GCRV activity in the C. idellus kidney cell line ( CIK ). The aim of this study was to test the potential application of EGCG as an anti‐ GCRV agent in aquaculture. Here, we demonstrate that various concentrations (99%, 50% and 35%) of EGCG could inhibit GCRV infectivity. EGCG (50%) + GCRV treatment significantly reduced the number of dead fish at 1‐, 2‐, 3‐, 4 ‐and 5‐day post‐challenge compared with the negative control ( GCRV challenge without EGCG treatment). The safety of EGCG compound products on cell survival was studied using four fish cell lines; we did not detect a significant change in cell viability within 24 hours of EGCG incubation. We also evaluated toxicity and concentrations of malondialdehyde ( MDA ), glutathione ( GSH ) and lysozyme ( LZM ) in the grass carp, and the results showed that even a high dose of EGCG did not induce toxicity. Following EGCG compound injection, the concentration of MDA decreased and the concentration of GSH and LZM increased compared with the control groups. We also detected EGCG concentration in grass carp plasma and kidney using HPLC with electrochemical detection after intraperitoneal injection at a dose of 150 mg/kg. The concentration of EGCG in the plasma and kidney reached the highest levels (20 μg/ ml and 1.5 μg/ ml ) about 12 hr after injection and then decreased. Overall, EGCG is a safe, effective product that could inhibit GCRV infection and improve immunoactivity in aquaculture.

Annual dynamics of impervious surfaces at city level of Pearl River Delta metropolitan - Ru Xu; Hongsheng Zhang; Hui Lin (International Journal of Remote Sensing, 2018)

Non-structural protein 1 from avian influenza virus H9N2 is an efficient RNA silencing suppressor with characteristics that differ from those of Tomato bushy stunt virus p19 - Ru Yu; Xiuli Jing; Wenjing Li; Jie Xu; Yang Xu; Liwei Geng; Changxiang Zhu; Hongmei Liu (Virus Genes, 2018)

Scopuquinolone B, a new monoterpenoid dihydroquinolin-2(1 H )-one isolated from the coral-derived Scopulariopsis sp. fungus - Xiao-Feng Mou; Xin Liu; Ru-Fang Xu; Mei-Yan Wei; Yao-Wei Fang; Chang-Lun Shao (Natural Product Research, 2018)

Genetic analysis of three porcine bocaparvoviruses and identification of a natural recombinant breakpoint in NS1 - Yu Zhou; Jia Xu; Shi-Kang Zhu; Qing-Feng Meng; Zhi-Xiong Lin; Ru Chen; Ai-Dong Qian (Archives of Virology, 2018)

CAT and MDH improve the germination and alleviate the oxidative stress of cryopreserved Paeonia and Magnolia pollen - Meng Xue Jia; Xue Ru Jiang; Jin Xu; Wei Di; Yin Shi; Yan Liu (Acta Physiologiae Plantarum, 2018)

A two-step leaching method designed based on chemical fraction distribution of the heavy metals for selective leaching of Cd, Zn, Cu, and Pb from metallurgical sludge - Fen Wang; Junxia Yu; Wanli Xiong; Yuanlai Xu; Ru-an Chi (Environmental Science and Pollution Research, 2018)

Pentapeptide-insertion scanning mutational analysis of turkey herpesvirus HVT063 reveals residues important for its RNA silencing suppression activity - Gang Jia; Wenjing Li; Meina Fan; Ru Yu; Yang Xu; Liwei Geng; Jiedao Zhang; Changxiang Zhu; Hongmei Liu (Archives of Virology, 2018)

UV‐B induced biosynthesis of a novel sunscreen compound in solar radiation and desiccation tolerant cyanobacteria - Jin‐Long Shang; Zhong‐Chun Zhang; Xiao‐Yue Yin; Min Chen; Fu‐Hua Hao; Kai Wang; Jun‐Li Feng; Hai‐Feng Xu; Yan‐Chao Yin; Hui‐Ru Tang; Bao‐Sheng Qiu (Environmental Microbiology, 2018)
Summary The small‐molecule sunscreen compounds, mycosporine‐like amino acids (MAAs), have strong ultraviolet (UV) absorption and can protect cyanobacteria against UV‐B damage. However, the molecular mechanism underlying UV‐B signaling and MAA chemical diversity remain largely unclear. Here, we identified a five‐gene cluster for MAA biosynthesis in the solar radiation and desiccation tolerant cyanobacterium Nostoc flagelliforme . A LuxR family protein OrrA was identified as a positive UV‐B responsive regulator binding to the promoter region of this gene cluster. OrrA functions as an activator mediating the UV‐B induced MAA biosynthesis. Overexpression of orrA strengthened its UV‐B tolerance during desiccation, and enhanced the photosynthetic recovery upon rehydration. Heterologous expression of this gene cluster in Anabaena PCC 7120 produces the same MAA as that in field samples of N . flagelliforme . The MAA structure is assigned as mycosporine‐2‐(4‐deoxygadusolyl‐ornithine) with a molecular weight of 756 Da, the structurally unique MAA compound reported to date. This MAA was catalyzed by mysD‐mysC2‐mysC1 encoding proteins from 4‐deoxygadusol, which was synthesized through the catalysis of mysA‐mysB products. Thus, we elucidated the transcriptional mechanism for a novel type MAA biosynthesis in solar radiation and desiccation tolerant cyanobacteria, which shed light on the identification of other components for UV‐B signaling in cyanobacteria.

Role of early environmental enrichment on the social dominance tube test at adulthood in the rat - Wen-Yu Cao; Zhao-Lan Hu; Yang Xu; Wen-Juan Zhang; Fu-Lian Huang; Xiao-Qing Qiao; Yan-Hui Cui; Wei Wan; Xue-qin Wang; Dan Liu; Ru-Ping Dai; Fang Li; et al. (Psychopharmacology, 2017)

ROS-induced oxidative stress is closely related to pollen deterioration following cryopreservation - Meng Xue Jia; Yin Shi; Wei Di; Xue Ru Jiang; Jin Xu; Yan Liu (In Vitro Cellular & Developmental Biology - Plant, 2017)

Selective adsorption and recycle of Cu2+ from aqueous solution by modified sugarcane bagasse under dynamic condition - Jia-dong Chen; Jun-xia Yu; Fen Wang; Jia-qi Tang; Yue-fei Zhang; Yuan-lai Xu; Ru-an Chi (Environmental Science and Pollution Research, 2017)

Impacts of climate variability and changes on domestic water use in the Yellow River Basin of China - Xiao-jun Wang; Jian-yun Zhang; Shahid Shamsuddin; Ru-lin Oyang; Tie-sheng Guan; Jian-guo Xue; Xu Zhang (Mitigation and Adaptation Strategies for Global Change, 2017)

Quantification of 3D macropore networks in forest soils in Touzhai valley (Yunnan, China) using X-ray computed tomography and image analysis - Jia-ming Zhang; Ze-min Xu; Feng Li; Ru-ji Hou; Zhe Ren (Journal of Mountain Science, 2017)

Improved salt tolerance of medicinal plant Codonopsis pilosula by Bacillus amyloliquefaciens GB03 - Qing-Qing Han; Yong-Na Wu; Hui-Juan Gao; Rui Xu; Paul W. Paré; Huazhong Shi; Qi Zhao; Hui-Ru Li; Sardar Ali Khan; Yin-Quan Wang; Suo-Min Wang; Jin-Lin Zhang (Acta Physiologiae Plantarum, 2017)

Over-expression of miR166a inhibits cotyledon formation in somatic embryos and promotes lateral root development in seedlings of Larix leptolepis - Zhe-Xin Li; Shui-Gen Li; Li-feng Zhang; Su-ying Han; Wan-Feng Li; Hai-yan Xu; Wen-hua Yang; Ya-li Liu; Yan-ru Fan; Li-Wang Qi (Plant Cell, Tissue and Organ Culture (PCTOC), 2016)

Salicylic acid-induced antioxidant protection against low temperature in cold-hardy winter wheat - Jing Yu; Jing Cang; Yanping Li; Ru Huang; Qiuwei Lu; Xiutian Wang; Lijie Liu; Qinghua Xu; Kejian Zhang (Acta Physiologiae Plantarum, 2016)

A genome-wide analysis of the ASYMMETRIC LEAVES2/LATERAL ORGAN BOUNDARIES (AS2/LOB) gene family in barley (Hordeum vulgare L.) - Bao-jian Guo; Jun Wang; Shen Lin; Zheng Tian; Kai Zhou; Hai-ye Luan; Chao Lyu; Xin-zhong Zhang; Ru-gen Xu (Journal of Zhejiang University-SCIENCE B, 2016)

Mild Hypothermia Combined with Hydrogen Sulfide Treatment During Resuscitation Reduces Hippocampal Neuron Apoptosis Via NR2A, NR2B, and PI3K-Akt Signaling in a Rat Model of Cerebral Ischemia-Reperfusion Injury - Hai-Bin Dai; Miao-Miao Xu; Jia Lv; Xiang-Jun Ji; Si-Hai Zhu; Ru-Meng Ma; Xiao-Lei Miao; Man-Lin Duan (Molecular Neurobiology, 2016)

Adsorption of Cd(II) by two variable-charge soils in the presence of pectin - Ru-hai Wang; Xiao-fang Zhu; Wei Qian; Min-hua Zhao; Ren-kou Xu; Yuan-chun Yu (Environmental Science and Pollution Research, 2016)

Effects of Interface Behavior on Fracture Spacing in Layered Rock - Xu Chang; Jianhua Wang; Chunan Tang; Zhongliang Ru (Rock Mechanics and Rock Engineering, 2016)

Neuroprotection of Sevoflurane Against Ischemia/Reperfusion-Induced Brain Injury Through Inhibiting JNK3/Caspase-3 by Enhancing Akt Signaling Pathway - Xiang-Ru Wen; Yan-Yan Fu; Hong-Zhi Liu; Jian Wu; Xiao-Ping Shao; Xun-Bao Zhang; Man Tang; Yue Shi; Kai Ma; Fang Zhang; Yi-Wen Wang; Hui Tang; et al. (Molecular Neurobiology, 2016)

Erratum to: An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2016)

Impacts of economic growth and urbanization on CO2 emissions: regional differences in China based on panel estimation - Shi-Chun Xu; Zheng-Xia He; Ru-Yin Long; Wen-Xing Shen; Sheng-Bao Ji; Quan-Bao Chen (Regional Environmental Change, 2016)

Differential effects of general anesthetics on anxiety-like behavior in formalin-induced pain: involvement of ERK activation in the anterior cingulate cortex - Cong Luo; Yan-Ling Zhang; Wei Luo; Fiona H Zhou; Chang-Qi Li; Jun-Mei Xu; Ru-Ping Dai (Psychopharmacology, 2015)

An Up-regulation of IRF-1 After a Spinal Cord Injury: Implications for Neuronal Apoptosis - Jian Zhao; Chen Chen; Jian-Ru Xiao; Hai-Feng Wei; Xu-hui Zhou; Xing-Xing Mao; Wei-dong Zhang; Rong Qian; Xin-lei Chen; Ming-qing He; Xiao-Wei Yu; Jian Zhao (Journal of Molecular Neuroscience, 2015)
IRF-1, a kind of transcription factor, is expressed in many cell types, except in early embryonal cells. IRF-1 has played an essential role in various physiological and pathological processes, including tumor immune surveillance, viral infection, development of immunity system and pro-inflammatory injury. However, the expression and function of IRF-1 in spinal cord injury (SCI) are still unknown. In this study, we have performed an acute SCI model in adult rats and investigated the dynamic changes of IRF-1 expression in the spinal cord. Western blot have shown that IRF-1 protein levels gradually increased, reaching a peak at day 3 and then gradually declined to a normal level at day 14 after SCI. Double immunofluorescence staining showed that IRF-1 immunoreactivity was found in neurons, but not in astrocytes and microglia. Additionally, colocalization of IRF-1/active caspase-3 was detected in neurons. In vitro, IRF-1 depletion, by short interfering RNA, obviously decreases neuronal apoptosis. In conclusion, this is the first description of IRF-1 expression in spinal cord injury. Our results suggested that IRF-1 might play crucial roles in CNS pathophysiology after SCI.

Effect of pectin on adsorption of Cu(II) by two variable-charge soils from southern China - Ru-hai Wang; Xiao-fang Zhu; Wei Qian; Yuan-chun Yu; Ren-kou Xu (Environmental Science and Pollution Research, 2015)

Investigation on time-dependent behaviour and long-term stability of underground water-sealed cavern - Huan-ling Wang; Wei-ya Xu; Long Yan; Qing-xiang Meng; Ru-bin Wang; Hai-bin Zhao; Wei-chau Xie (European Journal of Environmental and Civil Engineering, 2015)

Invasive fungal infection in allogeneic hematopoietic stem cell transplant recipients: single center experiences of 12 years - Ji-min Shi; Xu-ying Pei; Yi Luo; Ya-min Tan; Ru-xiu Tie; Jing-song He; Wei-yan Zheng; Jie Zhang; Zhen Cai; Mao-fang Lin; He Huang (Journal of Zhejiang University-SCIENCE B, 2015)

Potent Antifouling Marine Dihydroquinolin-2(1H)-one-Containing Alkaloids from the Gorgonian Coral-Derived Fungus Scopulariopsis sp. - Chang-Lun Shao; Ru-Fang Xu; Chang-Yun Wang; Pei-Yuan Qian; Kai-Ling Wang; Mei-Yan Wei (Marine Biotechnology, 2015)

Paracercospora dictamnicola sp. nov. from China - Yang-Hui Ou; Ru-Jun Zhou; Jun-Fan Fu; Yue Yuan; Hai-Jiao Xu (Mycological Progress, 2015)

Antitumor Activity of DMAKO-05, a Novel Shikonin Derivative, and Its Metabolism in Rat Liver Microsome - Xu Zhang; Ru-Bing Wang; Wen Zhou; Sui Xiao; Qing-Qing Meng; Shao-Shun Li (AAPS PharmSciTech, 2015)

The influence of genetics factor on key growth traits and quantitative genetic analysis of sea cucumber Apostichopus Japonicus (Selenka) heat-resistant and fast-growing strain - Sicong Zhang; Hongsheng Yang; Shilin Liu; Libin Zhang; Xiaoshang Ru; Dongxue Xu (Aquaculture International, 2015)

A novel strategy for rapid quantification of 20( S )-protopanaxatriol and 20( S )-protopanaxadiol saponins in Panax notoginseng P. ginseng and P. quinquefolium - Fa-Xiang Xu; Cen Yuan; Jian-Bo Wan; Ru Yan; Hao Hu; Shao-Ping Li; Qing-Wen Zhang (Natural Product Research, 2015)

Increased prevalence of hepatitis C virus subtype 6a in China: a comparison between 2004–2007 and 2008–2011 - Xia Rong; Ru Xu; Huaping Xiong; Min Wang; Ke Huang; Qiuyu Chen; Chengyao Li; Qiao Liao; Jieting Huang; Wenjie Xia; Guangping Luo; Xin Ye; et al. (Archives of Virology, 2014)

Cloning and characterisation of a pepper aquaporin, CaAQP, which reduces chilling stress in transgenic tobacco plants - Yan-Xu Yin; Wei-Li Guo; Ying-Li Zhang; Jiao-Jiao Ji; Huai-Juan Xiao; Fei Yan; Yan-Yan Zhao; Wen-Chao Zhu; Ru-Gang Chen; Wei-Guo Chai; Zhen-Hui Gong (Plant Cell, Tissue and Organ Culture (PCTOC), 2014)

Prefrontal Control of Cerebellum-Dependent Associative Motor Learning - Hao Chen; Li Yang; Yan Xu; Guang-yan Wu; Juan Yao; Jun Zhang; Zhi-ru Zhu; Zhi-an Hu; Jian-feng Sui; Bo Hu (The Cerebellum, 2014)

Calycosin entered HUVECs and ameliorated AGEs-promoted cell apoptosis via the Bcl-2 pathway - You-Hua Xu; Jianfeng Xiong; Shan-Shan Wang; Dan Tang; Ru-Shang Wang; Quan Zhu (Journal of Natural Medicines, 2014)

Circulating microparticles in patients with coronary heart disease and its correlation with interleukin-6 and C-reactive protein - Ying Cui; Lihui Zheng; Ming Jiang; Ru Jia; Xiao Zhang; Qishan Quan; Guiqin Du; Dongjin Shen; Xiaodan Zhao; Wenying Sun; Hongwei Xu; Lijuan Huang (Molecular Biology Reports, 2013)

Ecological Risks Assessment and Pollution Source Identification of Trace Elements in Contaminated Sediments from the Pearl River Delta, China - Feng Li; Xiang-yun Zeng; Chang-hua Wu; Zhi-peng Duan; Yan-mao Wen; Guo-ru Huang; Xiao-lin Long; Min-Jian Li; Man-Jie Li; Jiang-Yu Xu (Biological Trace Element Research, 2013)

A new sesquiterpene lactone from Sarcandra glabra - Xiao-Ru Hu; Hai-Feng Wu; Xiao-Po Zhang; Jun-Shan Yang; Zhong Dai; Rui-Chao Lin; Xu-Dong Xu (Natural Product Research, 2013)

Analysis of B-Class Genes NAP3L3 and NAP3L4 in Narcissus tazetta var. chinensis - Xiao-Fang Li; Jing Xu; Ru Yang; Lin-Yan Jia; Xin-Jie Deng; Li-Jun Xiong; Xue-Ping Zhang; Qi Fang; Wei Zhang; Yue Sun; Ling Xu (Plant Molecular Biology Reporter, 2013)

SIRT1 interacts with metabolic transcriptional factors in the pancreas of insulin-resistant and calorie-restricted rats - Yong-Ru Chen; Yu-lin Lai; Shao-da Lin; Xi-tao Li; Yu-Cai Fu; Wen-Can Xu (Molecular Biology Reports, 2013)

Resolvin E1 Inhibits Neuropathic Pain and Spinal Cord Microglial Activation Following Peripheral Nerve Injury - Zhen-Zhong Xu; Temugin Berta; Ru-Rong Ji (Journal of Neuroimmune Pharmacology, 2013)

Analysis of average standardized SSR allele size supports domestication of soybean along the Yellow River - Ying-hui Li; Chen Zhang; Marinus J. M. Smulders; Wei Li; Yan-song Ma; Qu Xu; Ru-zhen Chang; Li-juan Qiu (Genetic Resources and Crop Evolution, 2013)

Increased α-tocotrienol content in seeds of transgenic rice overexpressing Arabidopsis γ-tocopherol methyltransferase - Gui-Yun Zhang; Ru-Ru Liu; Geng Xu; Peng Zhang; Yin Li; Ke-Xuan Tang; Guo-Hua Liang; Qiao-Quan Liu (Transgenic Research, 2013)

A simple method to prepare magnetic modified beer yeast and its application for cationic dye adsorption - Jun-Xia Yu; Li-Yan Wang; Ru-An Chi; Yue-Fei Zhang; Zhi-Gao Xu; Jia Guo (Environmental Science and Pollution Research, 2013)

Cloning and sequence analysis of chitin synthase gene fragments of Demodex mites - Ya-e Zhao; Zheng-hang Wang; Yang Xu; Ji-ru Xu; Wen-yan Liu; Meng Wei; Chu-ying Wang (Journal of Zhejiang University-SCIENCE B, 2012)

Characterization and molecular mapping of RsrR, a resistant gene to maize head smut - W. H. Li; X. D. Xu; G. Li; L. Q. Guo; S. W. Wu; Y. Jiang; H. Y. Dong; M. L. Weng; D. M. Jin; J. Y. Wu; Z. G. Ru; B. Wang (Euphytica, 2012)
Maize head smut (MHS) caused by the fungi Sporisorium reilianum (Kühn) Landon and Fullerton ( S. reilianum ) is the most serious disease occurred in China recently. There are only a few reports concerning the genetics of this disease and the resistant gene of maize. In this paper a new dominant resistant gene to MHS caused by the pathogen Shenyang-1 of S. reilianum was discovered from a newly developed resistant inbred line ‘R24’ and was named RsrR. RsrR gene was molecular tagged and mapped on the long arm of maize chromosome 1 via simple sequence repeat-bulked segregant analysis (SSR-BSA) and sequence related amplified polymorphism (SRAP)-BSA analysis, the nearest linkage marker is 2.5 cM apart from the RsrR gene. The gene RsrR has been transferred into two elite maize inbred lines, ‘Huangzao4’ and ‘Qi319’, through traditional hybridization and marker assisted selection. The converted lines can be used in maize MHS-resistance breeding.

Sequence and phylogenetic analysis of H7N3 avian influenza viruses isolated from poultry in China in 2011 - Wu Hai-bo; Lu Ru-feng; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Xu Li-hua; Wu Nan-ping; Guo Chao-tan (Archives of Virology, 2012)

Role of ROS/RhoA/PI3K/PKB Signaling in NS1619-Mediated Blood–Tumor Barrier Permeability Increase - Yan-Ting Gu; Yi-Xue Xue; Yan-Feng Wang; Jin-Hui Wang; Qian-Ru ShangGuan; Jia-Xu Zhang; Li-Juan Qin (Journal of Molecular Neuroscience, 2012)

The prevalence of CD33 and MS4A6A variant in Chinese Han population with Alzheimer’s disease - Yu-Lei Deng; Li-Hua Liu; Ying Wang; Hui-Dong Tang; Ru-Jing Ren; Wei Xu; Jian-Fang Ma; Li-Ling Wang; Jun-Peng Zhuang; Gang Wang; Sheng-Di Chen (Human Genetics, 2012)

Trends of grain yield and plant traits in Chinese maize cultivars from the 1950s to the 2000s - Xiaoke Ci; Mingshun Li; Jiashun Xu; Zhenyu Lu; Pengfei Bai; Gaolin Ru; Xiaoling Liang; Degui Zhang; Xinhai Li; Li Bai; Chuanxiao Xie; Zhuanfang Hao; et al. (Euphytica, 2012)

Genetic characterization of subtype H1 avian influenza viruses isolated from live poultry markets in Zhejiang Province, China, in 2011 - Hai-bo Wu; Chao-tan Guo; Ru-feng Lu; Li-hua Xu; En-kang Wo; Jin-biao You; Yi-ting Wang; Qiao-gang Wang; Nan-ping Wu (Virus Genes, 2012)

Characterization of a highly pathogenic H5N1 avian influenza virus isolated from ducks in Eastern China in 2011 - Wu Hai-bo; Guo Chao-tan; Lu Ru-feng; Xu Li-hua; Wo En-kang; You Jin-biao; Wang Yi-ting; Wang Qiao-gang; Wu Nan-ping (Archives of Virology, 2012)

Lead and cadmium-induced oxidative stress impacting mycelial growth of Oudemansiella radicata in liquid medium alleviated by microbial siderophores - Yan-ru Cao; Xi-yu Zhang; Jia-yu Deng; Qi-qi Zhao; Heng Xu (World Journal of Microbiology and Biotechnology, 2012)

Effect of heavy metal-solubilizing microorganisms on zinc and cadmium extractions from heavy metal contaminated soil with Tricholoma lobynsis - Ling-yun Ji; Wei-wei Zhang; Dong Yu; Yan-ru Cao; Heng Xu (World Journal of Microbiology and Biotechnology, 2012)

Sociodemographic characteristics and risk factor analysis of Demodex infestation (Acari: Demodicidae) - Ya-e Zhao; Na Guo; Meng Xun; Ji-ru Xu; Mei Wang; Duo-lao Wang (Journal of Zhejiang University-SCIENCE B, 2011)

Impacts of erucic acid and glucosinolate content on genetic relationships between protein content and fatty acids of rape seed across environments - Chun-Hai Shi; Wei-Dong Xu; Qian-Ru Yu; Hai-Zhen Zhang; Zhong-Wei Yang; Jian-Guo Wu (Euphytica, 2011)

Sex difference in QTc prolongation in chronic institutionalized patients with schizophrenia on long-term treatment with typical and atypical antipsychotics - Fu De Yang; Xiang Qun Wang; Xiu Ping Liu; Ke Xin Zhao; Wei Hong Fu; Xue Ru Hao; Xing Li Zhang; Guo Shu Huang; Sheng Cai Qu; Jing Shen Bai; Xu Feng Huang; Thomas R. Kosten; et al. (Psychopharmacology, 2011)

Comparison of the ameliorating effects on an acidic ultisol between four crop straws and their biochars - Jin-Hua Yuan; Ren-Kou Xu; Wei Qian; Ru-Hai Wang (Journal of Soils and Sediments, 2011)

Influence of dhaT mutation of K. pneumoniae on 1,3-propanediol fermentation - Yun-Zhen Xu; Ru-Chun Wu; Zong-Ming Zheng; De-Hua Liu (World Journal of Microbiology and Biotechnology, 2011)

Effect of neuronal excitotoxicity on Munc18-1 distribution in nuclei of rat hippocampal neuron and primary cultured neuron - Yan-Ping Zhang; Ping Wan; Hong-Quan Wang; Hong Zhao; Yu-Xia Xu; Ru Yang; Cui-Qing Zhu (Neuroscience Bulletin, 2011)

Expression of tyrosine kinase receptor C in the segments of the spinal cord and the cerebral cortex after cord transection in adult rats - Dong-Xiang Qian; Hong-Tian Zhang; Ying-Qian Cai; Peng Luo; Ru-Xiang Xu (Neuroscience Bulletin, 2011)

IL-6 −174G>C polymorphism and cancer risk: a meta-analysis involving 29,377 cases and 37,739 controls - Bin Xu; Xiao-Bing Niu; Zi-Dun Wang; Wei Cheng; Na Tong; Yuan-Yuan Mi; Zhi-Chao Min; Jun Tao; Peng-Chao Li; Wei Zhang; Hong-Fei Wu; Zheng-Dong Zhang; et al. (Molecular Biology Reports, 2011)

MeJA-inducible expression of the heterologous JAZ2 promoter from Arabidopsis in Populus trichocarpa protoplasts - Yin Wang; Guan-Jun Liu; Xiu-Feng Yan; Zhi-Gang Wei; Zhi-Ru Xu (Journal of Plant Diseases and Protection, 2011)

Development and Characterization of Microsatellite Markers for Genetic Analysis of the Swimming Crab, Portunus trituberculatus - Qianghua Xu; Ru Liu (Biochemical Genetics, 2011)

Comparison of Non-covalent Interactions Between a Series of N-Phosphoryl Dipeptide or Methyl Esters and Protein by Electrospray Ionization Mass Spectrometry - Li-ming Qiang; Ming-xiu Lü; Xu-ru Dong; Shu-xia Cao; Kui Lu; Yu-fen Zhao (International Journal of Peptide Research and Therapeutics, 2011)

Methylobacterium soli sp. nov. a methanol-utilizing bacterium isolated from the forest soil - Yan-Ru Cao; Qian Wang; Rong-Xian Jin; Shu-Kun Tang; Yi Jiang; Wen-Xiang He; Hang-Xian Lai; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2011)

Evaluation of seed storage-protein gene 5′ untranslated regions in enhancing gene expression in transgenic rice seed - Wen Xian Liu; Hua Liang Liu; Zhi Jian Chai; Xiu Ping Xu; Yan Ru Song; Le Qing Qu (Theoretical and Applied Genetics, 2010)

Rubellimicrobium roseum sp. nov., a Gram-negative bacterium isolated from the forest soil sample - Yan-Ru Cao; Yi Jiang; Qian Wang; Shu-Kun Tang; Wen-Xiang He; Quan-Hong Xue; Li-Hua Xu; Cheng-Lin Jiang (Antonie van Leeuwenhoek, 2010)

Glutamate enhances the surface distribution and release of Munc18 in cerebral cortical neurons - Ping Wan; Yan-Ping Zhang; Jie Yan; Yu-Xia Xu; Hong-Quan Wang; Ru Yang; Cui-Qing Zhu (Neuroscience Bulletin, 2010)

Differentiation of cryopreserved human umbilical cord blood-derived stromal cells into cells with an oligodendrocyte phenotype - Yong-Chun Luo; Hong-Tian Zhang; Hao-Yu Cheng; Zhi-Jun Yang; Yi-Wu Dai; Ru-Xiang Xu (In Vitro Cellular & Developmental Biology - Animal, 2010)

Livin abrogates apoptosis of SPC-A1 cell by regulating JNKI signaling pathway - Yu-Sheng Chen; Hong-Ru Li; Ming Lin; Gang Chen; Bao-Song Xie; Neng-Luan Xu; Li-Fang Lin (Molecular Biology Reports, 2010)

Investigations on boron levels in drinking water sources in China - Ren-ji Xu; Xiao-ru Xing; Qun-fang Zhou; Gui-bin Jiang; Fu-sheng Wei (Environmental Monitoring and Assessment, 2010)

Biotreatment of oily wastewater by rhamnolipids in aerated active sludge system - Hong-zi Zhang; Xu-wei Long; Ru-yi Sha; Guo-liang Zhang; Qin Meng (Journal of Zhejiang University-SCIENCE B, 2009)

Genesis and stability of the Zhoujiawan landslide, Three Gorges, China - Wen-jie Xu; Rui-lin Hu; Zhong-qi Yue; Ru-jiao Tan (Bulletin of Engineering Geology and the Environment, 2009)

Human mesenchymal stem cells-like cells as cellular vehicles for delivery of immunotoxin in vitro - Chang-chen Hu; Yi-quan Ke; Xin-lin Sun; Xiao-dan Jiang; Ru-xiang Xu; Jun Lv; Yu-sheng Wang; Ying-qian Cai; Ling-sha Qin; Yu-xi Zou (Biotechnology Letters, 2009)

Competitive displacement of the native species Bursaphelenchus mucronatus by an alien species Bursaphelenchus xylophilus (Nematoda: Aphelenchida: Aphelenchoididae): a case of successful invasion - Xin-Yue Cheng; Pei-Zhen Xie; Fei-Xue Cheng; Ru-Mei Xu; Bing-Yan Xie (Biological Invasions, 2009)

The Influence of Center of Rotation on the Assessment of Trabecular Bone Densitometric and Structural Properties - Zhi-Feng Sheng; Ru-Chun Dai; Xian-Ping Wu; Yu-Lin Ma; Kang Xu; Yu-Hai Zhang; Ye-Bin Jiang; Er-Yuan Liao (Annals of Biomedical Engineering, 2008)

Androgen receptor: a new player associated with apoptosis and proliferation of pancreatic beta-cell in type 1 diabetes mellitus - Ru-Jiang Li; Shu-Dong Qiu; Hai-Xu Wang; Hong Tian; Li-Rong Wang; Yong-Wei Huo (Apoptosis, 2008)

Protolith natures and U‐Pb sensitive high mass‐resolution ion microprobe (SHRIMP) zircon ages of the metabasites in Hainan Island, South China: Implications for geodynamic evolution since the late Precambrian - De‐Ru Xu; Bin Xia; Peng‐Chun Li; Guang‐Hao Chen; Ci Ma; Yu‐Quan Zhang (Island Arc, 2007)
Metabasites within the Paleozoic volcanic‐clastic sedimentary sequences in Hainan Island, South China, show large differences not only in the nature of protoliths, but also in zircon U‐Pb sensitive high mass‐resolution ion microprobe (SHRIMP) ages. The protoliths for the Tunchang area metabasites have intraoceanic arc geochemical affinities. In the east‐central island gabbroic to diabasic rocks and pillow lavas are also present, while the Bangxi area metabasites with back‐arc geochemical affinities in the northwest island consist of basaltic, gabbroic and/or picritic rocks. Three types of zircon domains/crystals in the Tunchang area metabasites are defined. Type 1 is comagmatic and yields concordant to approximately concordant 206 Pb/238 U ages ranging from 442.1 ± 13.7 Ma to 514.3 ± 30.2 Ma with a weighted U‐Pb mean age of 445 ± 10 Ma. Type 2 is inherited and yields a weighted 207 Pb/206 Pb mean age of 2488.1 ± 8.3 Ma. Type 3 is magmatic with a 207 Pb/206 Pb age of ca 1450 Ma. Magmatic zircons in the Bangxi area metabasites yield a weighted U‐Pb mean age of 269 ± 4 Ma. We suggest 450 Ma is the minimum age for crystallization of protoliths of the Tunchang area metabasites, because the age range of ca 440–514 Ma probably corresponds to both the time of igneous crystallization and the high‐temperature overprint. The presence of abundant inherited zircons strongly favors derivation of these rocks from a NMORB‐like mantle proximal to continental crust. A protolith age of ca 270 Ma for the Bangxi area metabasites probably records expansion of an epircontinental back‐arc basin and subsequent generation of a small oceanic basin. The presence of ophiolitic rocks with an age of ca 450 Ma, not only in Hainan Island, but also in the Yangtze block, highlights the fact that the South China Caledonian Orogeny was not intracontinental in nature, but characterized by an ocean‐related event.

Exsolution lamellae in a clinopyroxene megacryst aggregate from Cenozoic basalt, Leizhou Peninsula, South China: petrography and chemical evolution - Xiao-Long Huang; Yi-Gang Xu; Ching-Hua Lo; Ru-Cheng Wang; Chuan-Yong Lin (Contributions to Mineralogy and Petrology, 2007)

Establishment of an efficient Agrobacterium tumefaciens-mediated leaf disc transformation of Thellungiella halophila - Hong-Qing Li; Jie Xu; Lei Chen; Mei-Ru Li (Plant Cell Reports, 2007)

Application of Bayesian Regularized BP Neural Network Model for Trend Analysis, Acidity and Chemical Composition of Precipitation in North Carolina - Min Xu; Guangming Zeng; Xinyi Xu; Guohe Huang; Ru Jiang; Wei Sun (Water, Air, & Soil Pollution, 2006)

Small heat-shock protein 22 mutated in autosomal dominant Charcot-Marie-Tooth disease type 2L - Bei-sha Tang; Guo-hua Zhao; Wei Luo; Kun Xia; Fang Cai; Qian Pan; Ru-xu Zhang; Fu-feng Zhang; Xiao-min Liu; Biao Chen; Cheng Zhang; Lu Shen; et al. (Human Genetics, 2005)

Theoretical studies on the mechanism of primary electron transfer in the photosynthetic reaction center of Rhodobacter sphaeroides - Hong Xu; Ru-Bo Zhang; Shu-Hua Ma; Zheng-Wang Qu; Xing-Kang Zhang; Qi-Yuan Zhang (Photosynthesis Research, 2002)

The Vigna angularis complex: Genetic variation and relationships revealed by RAPD analysis, and their implications for in situ conservation and domestication - Ru-Qiang Xu; Norihiko Tomooka; Duncan A. Vaughan; Koji Doi (Genetic Resources and Crop Evolution, 2000)

Phylogeny of Vicia Subgenus Vicia (Fabaceae) Based on Analysis of RAPDs and RFLP of PCR-Amplified Chloroplast Genes - Elena Potokina; N. Tomooka; Duncan A. Vaughan; T. Alexandrova; Ru-Qiang Xu (Genetic Resources and Crop Evolution, 1999)